Plastic lenses for head mounted displays
The resin lens for head-mounted displays addresses clarity issues by controlling phase difference, fluorescent content, and photoelastic coefficient, providing clear images while maintaining lightweight and durable properties.
Patent Information
- Application Number
- JP2020190777
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-11-17
AI Technical Summary
Existing head-mounted displays using resin lenses suffer from image clarity issues due to birefringence, which is exacerbated by the use of polarized light, leading to reduced magnification and overlapping low and high images, while glass lenses, although providing clear images, are heavy.
A resin lens for head-mounted displays is developed with specific properties including an average phase difference within the effective diameter of 5 nm or less, controlled fluorescent substance content, a glass transition temperature between 120°C and 160°C, a photoelastic coefficient of 3.0×10^-12 Pa^-1 or less, and a methacrylic resin composition with controlled structural units to minimize birefringence and ensure clear image transmission.
The resin lens enables clear image transmission without double images, maintains lightweight properties, and reduces stress-induced birefringence, ensuring high image quality and durability in head-mounted displays.
Smart Images

Figure 0007603419000006 
Figure 0007603419000001 
Figure 0007603419000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin lens for a head mounted display. [Background technology]
[0002] In recent years, various electronic technologies known as VR (Virtual Reality) and AR (Augmented Reality) have rapidly developed, and head mounted display (HMD) products are becoming popular as image display devices for these technologies. Since head mounted displays are image display devices worn on the head, they are required to be small, lightweight, and comfortable to wear.
[0003] As a means for miniaturizing head mounted displays, a method has been proposed in which a lens is combined with a quarter wave plate and a reflective polarizing plate, and the polarization state of light after passing through the lens is changed to switch between reflection and transmission, causing the image to make one and a half round trips through a single lens (Patent Documents 1-2). For example, this method works as follows: A quarter-wave plate and a reflective polarizer are placed on the back of a lens with a partially reflective coating on the front surface, and the light that enters the front surface of the lens as circularly polarized light is converted to linearly polarized light by the quarter-wave plate after passing through the lens; this linearly polarized light is reflected by the reflective polarizer, and is converted again by the quarter-wave plate into the opposite circularly polarized light to the original, which enters the lens from the back surface and reaches the partially reflective coating on the front surface; the light that is reflected by the partially reflective coating and leaves the back surface of the lens is converted to linearly polarized light with a 90° difference in direction from the original by the quarter-wave plate, passes through the reflective polarizer, and enters the eye as an image. In this way, a high magnification and wide field of view can be obtained even in a thin optical module. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] U.S. Patent No. 6,563,638 [Patent Document 2] JP 2017-21321 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above-mentioned head mounted display, if the polarization state changes while passing through the lens, for example, after passing through the lens for the first time, some of the light will pass through the reflective polarizing plate, and images with low and high magnification will overlap, making it difficult to obtain a clear image. Although clear images can be obtained by using glass lenses with small birefringence, this is undesirable because it increases the weight. Therefore, it is desired to obtain clear images even with resin lenses, which are lightweight but generally prone to birefringence.
[0006] Therefore, an object of the present invention is to provide a resin lens for a head mounted display which can provide a clear image even in an optical system that uses polarized light. [Means for solving the problem]
[0007] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that the phase difference within the effective diameter caused by the birefringence of a resin lens, and more surprisingly, the content of fluorescent substance contained in the resin lens, affect the clarity of images displayed on a head-mounted display, leading to the present invention.
[0008] That is, the present invention is as follows. [1] The average absolute value of the phase difference within the effective diameter is 5 nm or less, The content of the fluorescent substance was calculated from the fluorescence intensity at a wavelength of 530 nm when the 2.0 mass% solution was dissolved in chloroform and measured at an excitation wavelength of 436 nm using the concentration-intensity conversion formula for the ethanol solution of fluorescein. 3.0 ×10 -9 In mol / L A resin lens for a head mounted display, , The head mounted display includes: Using polarized light, the image light is repeatedly reflected and transmitted multiple times. A resin lens for a head mounted display, comprising: [2] The resin lens for head mounted displays according to [1], having a glass transition temperature (Tg) of more than 120°C and not more than 160°C. [3] The absolute value of the photoelastic coefficient is 3.0×10 -12 Pa -1 The resin lens for a head mounted display according to [1] or [2] below. [4] The resin lens for a head mounted display according to any one of [1] to [3], which contains a methacrylic resin. [5] The resin lens for a head mounted display according to [4], wherein the methacrylic resin contains a methacrylic resin having a structural unit (X) having a ring structure in its main chain. [6] The resin lens for head mounted displays according to [5], wherein the structural unit (X) contains at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide structural unit, and a lactone ring structural unit. [7] The resin lens for head mounted displays according to [5], wherein the structural unit (X) contains a structural unit derived from an N-substituted maleimide monomer. [8] The resin lens for a head mounted display according to [5], wherein the structural unit (X) contains a glutarimide structural unit. Effect of the Invention
[0009] According to the present invention, it is possible to provide a resin lens for a head mounted display that can provide a clear image even in an optical system that uses polarized light. [Brief description of the drawings]
[0010] [Figure 1]1 is a schematic diagram of a simulator that reproduces the principle of a head-mounted display described in JP 2017-21321 A. In the examples, the simulator was used to evaluate the clarity of images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiment of the present invention (hereinafter referred to as the present embodiment) will be described in detail. However, the present invention is not limited to the following description, and various modifications may be made within the scope of the present invention. It can be implemented with modifications.
[0012] [Resin lenses for head mounted displays] The resin lens for head mounted displays of this embodiment has an average absolute value of phase difference within an effective diameter of 5 nm or less, and a content of a fluorescent substance calculated from a fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving the lens in chloroform is measured at an excitation wavelength of 436 nm using a concentration-intensity conversion formula for a fluorescein ethanol solution of 0.1 to 4.0 × 10 -9 It is characterized by being mol / L.
[0013] - Phase difference within the effective diameter - In the resin lens for head mounted displays in this embodiment, the average absolute value of the phase difference within the effective diameter of the resin lens is 5 nm or less, preferably 4 nm or less, and more preferably 3 nm or less. By having the average absolute value of the phase difference of 5 nm or less, the image can be clearly viewed without being doubled. Here, the effective diameter of the resin lens represents the range in which an image can be viewed when the lens is incorporated into the housing of a head mounted display, and is expressed as the diameter of a circle centered on the optical axis of the lens. If the range in which the image can be viewed is not a perfect circle, the minor axis is taken as the effective diameter. The phase difference within the effective diameter of the resin lens can be specifically measured by the method described in the Examples below.
[0014] -Fluorescent substance content- In the present embodiment, the resin lens for head mounted displays has a content of a fluorescent substance of 0.1 to 4.0 × 10, which is calculated from the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving the resin lens in chloroform is measured at an excitation wavelength of 436 nm, using a concentration-intensity conversion formula for a fluorescein ethanol solution. -9 mol / L, preferably 0.2 to 3.5×10 -9 mol / L, more preferably 0.3 to 3.0×10 -9 mol / L, more preferably 0.3 to 2.5×10 -9 mol / L. By making the content of the fluorescent substance equal to or less than the upper limit, the image can be clearly viewed without blurring. Also, by making the content of the fluorescent substance equal to or more than the lower limit, it is possible to prevent low-wavelength light, which is harmful to the eyes, from entering the eyes more than necessary. Although it is unclear why images appear blurry when the fluorescence intensity is high (high content of fluorescent substances), it is presumed that when fluorescence is generated by light passing through the lens, the image appears blurry because the light is directed in a direction other than the original traveling direction of the transmitted light. Furthermore, in lenses for head-mounted displays that use polarized light and are repeatedly reflected and pass through the lens multiple times, it is presumed that the blurring of images becomes more noticeable because the optical path length passing through the lens becomes longer and the deviation from the original traveling direction of the light becomes larger due to the reflective polarizing plate and partial reflection coating. The content of the fluorescent substance can be specifically measured by the method described in the Examples below.
[0015] -Glass transition temperature- The glass transition temperature (Tg) of the resin lens for head mounted displays in this embodiment is preferably higher than 120° C. and 160° C. or lower. From the viewpoint of heat resistance against heat generated from electronic devices of the head mounted display and from the viewpoint of occurrence of photoelastic birefringence due to dimensional change, it is preferable that the glass transition temperature of the resin lens for the head mounted display exceeds 120° C. From the viewpoint of dimensional stability under the temperature of the usage environment, the glass transition temperature (Tg) is more preferably 125° C. or higher, and further preferably 130° C. or higher. On the other hand, when the glass transition temperature (Tg) is 160° C. or lower, melt processing at extremely high temperatures is avoided, thermal decomposition of the resin, etc. is suppressed, and a good product can be obtained. From the viewpoint of further obtaining the above-mentioned effects, the glass transition temperature (Tg) is preferably 150° C. or lower, more preferably 140° C. or lower. The glass transition temperature (Tg) can be determined by measurement in accordance with JIS-K7121. Specifically, it can be determined by the method described in the Examples below.
[0016] - Photoelastic coefficient C R - Photoelastic coefficient C of the resin lens for the head mounted display of this embodiment R Absolute value of |C R | is 3.0 x 10 -12 Pa -1 It is preferable that the ratio is 2.0×10 or less, and more preferable that the ratio is 2.0×10 -12 Pa -1 More preferably, it is 1.5×10 -12 Pa -1 More preferably, it is 1.0×10 -12 Pa -1 The photoelastic coefficient is described in various publications (for example, see Chemical Review, No. 39, 1998 (published by the Academic Press Center)) and is defined by the following formulas (ia) and (ib). R It can be seen that the closer the value of is to zero, the smaller the change in birefringence due to an external force is. |C R |=|Δn| / σ R (ia) |Δn|=|nx-ny| (ib) (In the formula, C R is the photoelastic coefficient, σR is the stretching stress, |Δn| is the absolute value of birefringence, nx is the refractive index in the stretching direction, and ny is the refractive index in the in-plane direction perpendicular to the stretching direction.) Photoelastic coefficient C of the resin lens of this embodiment R Absolute value of |C R | is 3.0×10 -12 Pa -1 If it is within this range, the stress generated when fixing the lens and the photoelastic birefringence generated due to dimensional changes caused by temperature are sufficiently small, and a resin lens that can provide a clear image can be obtained. In addition, the photoelastic coefficient C R The measurement of is carried out by cutting the resin lens into small pieces and pressing the pieces into a press film using a vacuum compression molding machine. Specifically, it can be determined by the method described in the Examples below.
[0017] -Light transmittance- In the resin lens for head mounted displays of this embodiment, the ratio (T450 / T680) of the light transmittance at the thickest part measured with a spectrophotometer under a D65 light source and a 10° field of view is preferably 0.95 to 1.03, more preferably 0.97 to 1.01, and even more preferably 0.98 to 1.00, of the transmittance (T450) at a wavelength of 450 nm to the transmittance (T680) at a wavelength of 680 nm. When the ratio (T450 / T680) is within the above range, an image with good color tone can be obtained. The light transmittance can be measured by the method described in the Examples below.
[0018] -Molecular weight and molecular weight distribution- The resin lens for head mounted displays in this embodiment has a weight average molecular weight (Mw) in terms of polymethyl methacrylate measured by gel permeation chromatography (GPC) in the range of preferably 80,000 to 170,000, more preferably 100,000 to 170,000, even more preferably 100,000 to 150,000, and still more preferably 120,000 to 150,000. When the weight average molecular weight (Mw) is in the above range, the balance between mechanical strength and fluidity is excellent.
[0019] The weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) of the resin lens can be measured using the following device and conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500, connected in series. Column temperature: 40℃ Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard at 0.1 g / L. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Sample: 0.02 g of resin lens dissolved in 20 mL of tetrahydrofuran Injection volume: 10μL Standard sample for calibration curve: The following 10 types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse weight peak molecular weights and different molecular weights are used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity is measured versus the elution time of the resin lens. Based on each calibration curve obtained by measuring the standard samples for the calibration curve, the weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) of the resin lens are determined, and the molecular weight distributions (Mw / Mn) and (Mz / Mw) are determined using these values.
[0020] -Methanol insolubles- The ratio of the amount of methanol insoluble matter in the resin lens for head mounted displays in this embodiment to the total amount 100% by mass of the amount of methanol insoluble matter and the amount of methanol soluble matter is preferably 95% by mass or more, more preferably 95.5% by mass or more, even more preferably 96% by mass or more, still more preferably 96.5% by mass or more, particularly preferably 97% by mass or more, and most preferably 97.5% by mass or more. By making the ratio of the amount of methanol insoluble matter 95% by mass or more, it is possible to suppress molding troubles such as the generation of silver streaks during injection molding. The methanol-insoluble fraction and the methanol-soluble fraction refer to those obtained by dissolving a resin lens for a head mounted display in chloroform to prepare a chloroform solution, dropping the solution into a large excess of methanol to effect reprecipitation, separating the filtrate and the residue, and then drying each of them.
[0021] Specifically, it can be obtained as follows. After dissolving 5 g of resin lens in 100 mL of chloroform, the solution is placed in a dropping funnel and dropped into 1 L of methanol stirred with a stirrer for about 1 hour to perform reprecipitation. After dropping the entire amount, it is left to stand for 1 hour, and then suction filtration is performed using a membrane filter (Advantec Toyo Co., Ltd., T050A090C) as a filter. The filtrate is vacuum dried at 60°C for 16 hours to obtain methanol insoluble matter. In addition, the filtrate is subjected to a rotary evaporator with a bath temperature of 40°C and a vacuum degree gradually reduced from the initial setting of 390 Torr to a final value of 30 Torr to remove the solvent, and the soluble matter remaining in the eggplant-shaped flask is collected to obtain methanol soluble matter. The mass of the methanol insoluble matter and the mass of the methanol soluble matter are each weighed, and the ratio (mass%) of the amount of the methanol soluble matter to the total amount (100 mass%) of the amount of the methanol soluble matter and the amount of the methanol insoluble matter is calculated (methanol soluble matter ratio).
[0022] [Resin composition] The resin lens for a head mounted display of the present embodiment is preferably made of a resin composition containing a methacrylic resin.
[0023] [Methacrylic resin] The methacrylic resin contained in the resin lens for head mounted display of this embodiment preferably contains a methacrylic resin having a structural unit (X) having a ring structure in the main chain and a structural unit derived from a methacrylic acid ester monomer. By containing a methacrylic resin, particularly a methacrylic resin containing a structural unit (X) having a ring structure in the main chain and a methacrylic acid ester monomer unit, it is possible to obtain a resin lens having a sufficiently small phase difference within the effective diameter of the lens and a sufficiently small photoelastic coefficient.
[0024] Each structural unit will be described below.
[0025] -Structural units derived from methacrylate ester monomers- Examples of structural units derived from methacrylic acid ester monomers include structural units derived from monomers selected from the methacrylic acid esters shown below. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, and 2,4,6-tribromophenyl methacrylate. These monomers may be used alone or in combination of two or more kinds. As the structural units derived from the methacrylic acid ester monomer, structural units derived from methyl methacrylate and benzyl methacrylate are preferred in that the resulting methacrylic resin has excellent transparency and weather resistance. The structural unit derived from the methacrylic acid ester monomer may be contained in only one type, or in two or more types.
[0026] In the resin lens for head mounted displays of the present embodiment, the ratio of the structural unit (X) having a ring structure in the main chain and the structural unit derived from the methacrylic acid ester monomer is appropriately adjusted to reduce birefringence caused by orientation during molding or residual stress, and a resin lens for head mounted displays having an average absolute value of retardation within the effective diameter of 5 nm or less can be obtained. In addition, by appropriately adjusting the above ratio, sufficient heat resistance can be imparted to the methacrylic resin. From these viewpoints, the content of the structural unit derived from the methacrylic acid ester monomer is preferably 50 to 97% by mass, more preferably 55 to 97% by mass, even more preferably 55 to 95% by mass, even more preferably 60 to 93% by mass, and particularly preferably 60 to 90% by mass, based on 100% by mass of the methacrylic resin. The content of structural units derived from methacrylic acid ester monomers is 1 H-NMR measurement and 13 It can be determined by C-NMR measurement. 1 H-NMR measurement and 13 C-NMR measurement can be carried out, for example, using CDCl3 or DMSO-d6 as a measurement solvent at a measurement temperature of 40°C.
[0027] The structural unit (X) having a ring structure in the main chain will be described below. The structural unit (X) having a ring structure in the main chain preferably contains at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units, and lactone ring structural units, and more preferably consists of at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units, and lactone ring structural units. The structural unit (X) having a ring structure in the main chain may be one type or a combination of multiple types.
[0028] -Structural unit derived from N-substituted maleimide monomer- Next, the structural unit derived from the N-substituted maleimide monomer will be described. The structural unit derived from the N-substituted maleimide monomer may be at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), and is preferably formed from both of the structural units represented by the following formula (1) and the following formula (2).
[0029] [ka] In formula (1), R 1 represents an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms; R 2 and R 3 each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms. Also, R2 or R 3 When is an aryl group, R 2 or R 3 may contain a halogen atom as a substituent. Also, R 1 may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group. [ka] In formula (2), R 4 represents a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, or an alkyl group having 1 to 12 carbon atoms; R 5 and R 6 each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.
[0030] Specific examples are given below. Examples of monomers (N-arylmaleimides, N-aromatic substituted maleimides, etc.) that form the structural unit represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-phenyl ... N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthracenylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, and the like. Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred because the resulting methacrylic resin has excellent heat resistance and optical properties such as birefringence. These monomers may be used alone or in combination of two or more kinds.
[0031] Examples of the monomer that forms the structural unit represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, Ns-butylmaleimide, Nt-butylmaleimide, Nn-pentylmaleimide, Nn-hexylmaleimide, Nn-heptylmaleimide, Nn-octylmaleimide, and N- Examples of the maleimide include laurylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, and 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione. Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred because they provide excellent weather resistance to the methacrylic resin, and N-cyclohexylmaleimide is particularly preferred because it has excellent low moisture absorption, which is a requirement for optical materials in recent years. These monomers can be used alone or in combination of two or more.
[0032] In the methacrylic resin of this embodiment, the structural unit represented by formula (1) and the structural unit represented by formula (2) are used in combination to exhibit highly controlled birefringence characteristics. The above is particularly preferred. The molar ratio (X1 / X2) of the content (X1) of the structural unit represented by formula (1) to the content (X2) of the structural unit represented by formula (2) is preferably more than 0 and 15 or less, more preferably more than 0 and 10 or less. When the molar ratio (X1 / X2) is within this range, the resin lens of this embodiment maintains its transparency, is not yellowed, and does not lose its environmental resistance, and exhibits good heat resistance and good photoelastic properties.
[0033] The content of the structural unit derived from the N-substituted maleimide monomer is preferably in the range of 5 to 40% by mass, and more preferably in the range of 5 to 35% by mass, based on 100% by mass of the methacrylic resin. Within this range, the methacrylic resin can obtain a more sufficient improvement in heat resistance, and can obtain more preferable improvements in weather resistance, low water absorption, and optical properties. In addition, keeping the content of structural units derived from N-substituted maleimide monomers to 40 mass% or less is effective in preventing a decrease in the physical properties of the methacrylic resin due to a decrease in the reactivity of the monomer component during the polymerization reaction and an increase in the amount of unreacted remaining monomer. In addition, by appropriately adjusting the content of the structural units derived from the N-substituted maleimide monomer within this range, it is possible to reduce birefringence caused by orientation during molding or residual stress, and obtain a resin lens for a head mounted display having an average absolute value of retardation within an effective diameter of 5 nm or less. The optimal content of the structural units derived from the N-substituted maleimide monomer varies depending on the type of N-substituted maleimide, but for example, when methyl methacrylate is used as the methacrylic acid ester monomer and N-phenylmaleimide and N-cyclohexylmaleimide are used as the N-substituted maleimide monomer, it is preferable to adjust the content within the range of 79 to 83 mass% of the structural units derived from methyl methacrylate, 6 to 8 mass% of the structural units derived from N-phenylmaleimide, and 11 to 13 mass% of the structural units derived from N-cyclohexylmaleimide.
[0034] The methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, which constitutes the resin lens for head mounted displays of the present embodiment, may contain a structural unit derived from another monomer copolymerizable with the methacrylic acid ester monomer and the N-substituted maleimide monomer, within a range not impairing the object of the present invention. For example, the other copolymerizable monomers include aromatic vinyls; unsaturated nitriles; acrylic esters having a cyclohexyl group, a benzyl group, or an alkyl group having 1 to 18 carbon atoms; glycidyl compounds; and unsaturated carboxylic acids. Examples of the aromatic vinyl include styrene, α-methylstyrene, and divinylbenzene. Examples of the unsaturated nitrile include acrylonitrile, methacrylonitrile, and ethacrylonitrile. Examples of the acrylic ester include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, and butyl acrylate. The glycidyl compound includes glycidyl (meth)acrylate and the like. The unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and half-esters or anhydrides thereof. The structural unit derived from the other copolymerizable monomer may be of only one type, or may be of two or more types.
[0035] The content of structural units derived from these other copolymerizable monomers is preferably 0 to 10 mass%, more preferably 0 to 9 mass%, and even more preferably 0 to 8 mass%, based on 100 mass% of the methacrylic resin. It is preferable that the content of the structural units derived from other monomers is within this range, since it is possible to improve the molding processability and mechanical properties of the resin without impairing the inherent effect of introducing a ring structure into the main chain.
[0036] The content of the structural unit derived from the N-substituted maleimide monomer and the content of the structural unit derived from other copolymerizable monomers are as follows: 1 H-NMR measurement and 13 It can be determined by C-NMR measurement. 1 H-NMR measurement and 13 C-NMR measurement can be carried out, for example, using CDCl3 or DMSO-d6 as a measurement solvent at a measurement temperature of 40°C.
[0037] -Glutarimide structural unit- Examples of methacrylic resins having glutarimide structural units in the main chain include methacrylic resins having glutarimide structural units described in JP-A-2006-249202, JP-A-2007-009182, JP-A-2007-009191, JP-A-2011-186482, and Republished Patent Publication No. 2012 / 114718, and can be formed by the methods described in these publications. The glutarimide structural unit constituting the methacrylic resin of the present embodiment may be formed after polymerization of the resin. Specifically, the glutarimide structural unit may be represented by the following general formula (3).
[0038] [ka] In the above general formula (3), preferably R 7 and R 8 are each independently a hydrogen atom or a methyl group, R 9 is any one of a hydrogen atom, a methyl group, a butyl group, and a cyclohexyl group, and more preferably, R 7 is a methyl group, and R 8 is a hydrogen atom, and R 9 is a methyl group. The glutarimide-based structural unit may include only one type, or may include a plurality of types.
[0039] In the methacrylic resin having a glutarimide structural unit, the content of the glutarimide structural unit is preferably in the range of 3 to 70 mass %, more preferably in the range of 3 to 60 mass %, based on 100 mass % of the methacrylic resin. It is preferable that the content of the glutarimide structural unit is within the above range, since a resin having good moldability, heat resistance, and optical properties can be obtained. In addition, by appropriately adjusting the content of the glutarimide-based structural unit within this range, it is possible to reduce birefringence caused by orientation during molding or residual stress, and obtain a resin lens for a head mounted display having an average absolute value of retardation within the effective diameter of 5 nm or less. 7 ~R 9 The optimum content of glutarimide-based structural units varies depending on the type of the substituent of R. 7 and R 8 is a hydrogen atom, R 9 When is a methyl group, if the content of the glutarimide structural unit is in the range of 3 to 10 mass %, birefringence caused by orientation or residual stress during molding can be reduced, and a resin lens for head mounted displays having an average absolute value of retardation within the effective diameter of 5 nm or less can be obtained. The content of glutarimide structural units in the methacrylic resin can be determined by the method described in the aforementioned patent document.
[0040] The methacrylic resin having a glutarimide structural unit may further contain an aromatic vinyl monomer unit, if necessary. The aromatic vinyl monomer is not particularly limited, but examples thereof include styrene and α-methylstyrene, with styrene being preferred.
[0041] The content of aromatic vinyl units in the methacrylic resin having glutarimide structural units is not particularly limited, but is preferably 0 to 20% by mass, with the methacrylic resin having glutarimide structural units being 100% by mass. When the content of the aromatic vinyl unit is within the above range, it is possible to achieve both heat resistance and excellent photoelasticity properties, which is preferable. For example, when a resin is obtained by glutarimidating a methyl methacrylate-styrene copolymer obtained by copolymerizing methyl methacrylate as the methacrylic acid ester monomer and styrene as the aromatic vinyl monomer, by adjusting the ranges of 25 to 90 mass% of structural units derived from methyl methacrylate, 5 to 15 mass% of structural units derived from styrene, and 5 to 70 mass% of glutarimide-based structural units, it is possible to reduce birefringence caused by orientation and residual stress during molding and to obtain a resin lens for a head mounted display having an average absolute value of retardation within the effective diameter of 5 nm or less.
[0042] -Lactone ring structural unit- Methacrylic resins having a lactone ring structural unit in the main chain can be formed by the methods described in, for example, JP-A Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.
[0043] The lactone ring structural unit constituting the methacrylic resin of the present embodiment may be formed after polymerization of the resin. The lactone ring structural unit in this embodiment is preferably a six-membered ring because this provides excellent stability of the ring structure. As the 6-membered lactone ring structural unit, for example, a structure represented by the following general formula (4) is particularly preferred.
[0044] [ka] In the above general formula (4), R 10 , R 11 and R 12 are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms. Examples of the organic residue include saturated aliphatic hydrocarbon groups (alkyl groups, etc.) having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, a propyl group, etc.; unsaturated aliphatic hydrocarbon groups (alkenyl groups, etc.) having 2 to 20 carbon atoms, such as an ethenyl group, a propenyl group, etc.; aromatic hydrocarbon groups (aryl groups, etc.) having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, etc.; and groups in which one or more hydrogen atoms in these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups have been substituted with at least one group selected from the group consisting of a hydroxy group, a carboxyl group, an ether group, and an ester group.
[0045] The lactone ring structural unit can be formed, for example, by copolymerizing an acrylic acid monomer having a hydroxy group with a methacrylic acid ester monomer such as methyl methacrylate to introduce a hydroxy group and an ester group or a carboxyl group into the molecular chain, and then causing dealcoholization (esterification) or dehydration condensation (hereinafter also referred to as a "cyclization condensation reaction") between the hydroxy group and the ester group or the carboxyl group.
[0046] Examples of the acrylic acid monomer having a hydroxy group used in the polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, 2-(hydroxymethyl)alkyl acrylates (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, t-butyl 2-(hydroxymethyl)acrylate), and 2-(hydroxyethyl)alkyl acrylates. Preferred are 2-(hydroxymethyl)acrylic acid and 2-(hydroxymethyl)alkyl acrylates, which are monomers having a hydroxyalkyl moiety, and particularly preferred are methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate.
[0047] The content of the lactone ring structural unit in the methacrylic resin having the lactone ring structural unit in the main chain is preferably 5 to 40 mass %, and more preferably 5 to 35 mass %, relative to 100 mass % of the methacrylic resin. When the content of the lactone ring structural unit is within this range, the effects of introducing a ring structure, such as improved solvent resistance and improved surface hardness, can be achieved while maintaining moldability. In addition, by appropriately adjusting the content of the lactone ring structural unit within this range, it is possible to reduce birefringence caused by orientation and residual stress during molding, and to obtain a resin lens for a head mounted display having an average absolute value of retardation within the effective diameter of 5 nm or less. The content of the lactone ring structure in the methacrylic resin can be determined by the method described in the aforementioned patent document.
[0048] The methacrylic resin having a lactone ring structural unit in the main chain may have a structural unit derived from another monomer copolymerizable with the above-mentioned methacrylic acid ester monomer and the acrylic acid monomer having a hydroxy group. Examples of such other copolymerizable monomers include monomers having a polymerizable double bond, such as styrene, vinyl toluene, α-methyl styrene, α-hydroxymethyl styrene, α-hydroxyethyl styrene, acrylonitrile, methacrylonitrile, methallyl alcohol, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, and N-vinyl carbazole. The copolymer may contain only one type of these other monomers (structural units), or may contain two or more types.
[0049] The content of structural units derived from these other copolymerizable monomers is preferably 0 to 20 mass% relative to 100 mass% of the methacrylic resin, and from the viewpoint of weather resistance, it is more preferably less than 10 mass%, and even more preferably less than 7 mass%. The methacrylic resin in the present embodiment may have only one type of structural unit derived from the other copolymerizable monomer, or may have two or more types.
[0050] The methacrylic resin in this embodiment preferably has at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units, and lactone ring structural units, and among them, it is particularly preferable to have structural units derived from N-substituted maleimide monomers, in particular from the viewpoint of easily controlling optical properties such as photoelastic coefficient without blending with other thermoplastic resins.Furthermore, in particular from the viewpoint of obtaining a resin lens with high strength, it is particularly preferable to have glutarimide structural units.
[0051] [Methacrylic resin manufacturing method] Hereinafter, the method for producing the methacrylic resin of this embodiment will be described.
[0052] -Method for producing methacrylic resin containing structural units derived from N-substituted maleimide monomer- Examples of a production method for a methacrylic resin having structural units derived from an N-substituted maleimide monomer in the main chain (hereinafter, may be referred to as a "maleimide copolymer") include bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, and emulsion polymerization. From the viewpoint of reducing the amount of residual monomer and impurities contained in the resin lens, suspension polymerization, bulk polymerization, and solution polymerization are preferred, and solution polymerization is more preferred.
[0053] In the production method of the present embodiment, any of a batch polymerization method, a semi-batch polymerization method, and a continuous polymerization method can be used as the polymerization method. In this embodiment, a method in which a part of the monomer is charged into a reactor before the start of polymerization, a polymerization initiator is added to start the polymerization, and then the remainder of the monomer is supplied, that is, a so-called semi-batch polymerization method, is used, from the viewpoint of reducing the amount of maleimide remaining at the end of polymerization and decreasing the fluorescence intensity (reducing the content of the fluorescent substance).
[0054] In a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, methods for controlling the resulting resin lens to exhibit a predetermined fluorescence intensity (the content of the fluorescent substance to be within a predetermined range) include at least one selected from (1) using, as a raw material, an N-substituted maleimide monomer having a controlled content of specific impurities, (2) applying a polymerization method that reduces the amount of unreacted N-substituted maleimide remaining after completion of polymerization, and (3) applying a devolatilization method that reduces shear, and among these, it is preferable to select a production method that combines (1) and (3), or a production method that combines all three.
[0055] (1) Control of impurities in N-substituted maleimides One of the impurities in N-substituted maleimide that gives fluorescence to methacrylic resin is 2-amino-N-substituted succinimide produced by the reaction of N-substituted maleimide with primary amine. Examples of 2-amino-N-substituted succinimide include 2-cyclohexylamino-N-cyclohexyl succinimide and 2-anilino-N-phenyl succinimide. Not only does 2-amino-N-substituted succinimide itself have fluorescence, but the inventors have found that when it is heated to 300°C or higher or subjected to a volatilizer having shear, a thermally denatured product having fluorescence is produced, although the detailed denaturation mechanism is unknown. That is, in order to control the fluorescence intensity of the methacrylic resin and the resulting resin lens, it is preferable to reduce the amount of 2-amino-N-substituted succinimide contained in the N-substituted maleimide and to use a volatilizer without a rotating part in the production of the methacrylic resin and perform volatilization at 300°C or lower.
[0056] As a method for controlling impurities in the N-substituted maleimide, a pretreatment step of washing the N-substituted maleimide with water (water washing step) and / or dehydrating the N-substituted maleimide with water (dehydration step) can be provided. The pretreatment step may be only washing with water, or a combination of washing with water and dehydration. In addition, washing with water and dehydration may be performed once each, or multiple times. The pretreatment step may further include a concentration adjustment step for adjusting the concentration of the N-substituted maleimide solution obtained in the dehydration step.
[0057] In the present embodiment, for example, 2-amino-N-substituted succinimide in the N-substituted maleimide is removed by a water washing step described below, and then water is removed by a dehydration step, whereby an N-substituted maleimide solution suitable for preparing a methacrylic resin having controlled fluorescence intensity and good color tone can be obtained. In the water-washing step, for example, a method can be employed in which the N-substituted maleimide is dissolved in a water-insoluble organic solvent, separated into an organic layer and an aqueous layer, the organic layer is mixed and washed with one or more liquids selected from an acidic aqueous solution, water and an alkaline aqueous solution by a batch system, a continuous system, or both systems, and then the organic layer and the aqueous layer are separated.
[0058] The amount of 2-amino-N-substituted succinimide in the organic layer after the water washing step is preferably 5 ppm by mass or less, more preferably 0.1 ppm by mass or more and 1 ppm by mass or less, when the amount of N-substituted maleimide in the organic layer is taken as 100% by mass. When the amount of 2-amino-N-substituted succinimide in the organic layer is within this range, the concentration of the fluorescent substance in the methacrylic resin and the obtained resin lens can be controlled within the above-mentioned range, and a resin lens for a head mounted display that can obtain a clear image can be obtained, which is preferable. It is also preferable in terms of the cost of washing. When the dehydration step is not provided, the organic layer containing the N-substituted maleimide obtained in the water washing step may be used in the polymerization step as an N-substituted maleimide solution. The amount of 2-amino-N-substituted succinimide in the organic layer can be measured, for example, by gas chromatography, liquid chromatography, or the like using isopropyl benzoate as an internal standard substance. Specifically, it can be measured by the method described in the Examples below.
[0059] The water-insoluble organic solvent to be used is not particularly limited as long as it dissolves the N-substituted maleimide and the 2-amino-N-substituted succinimide, undergoes phase separation from water, and has an azeotropic point with water.Specific examples of the water-insoluble organic solvent that can be used include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as normal hexane and cyclohexane, and halogenated hydrocarbons such as chloroform and dichloroethane. The water used may be sewage water, pure water, or clean water. The acidity of the acidic aqueous solution or the alkaline aqueous solution is not particularly limited.
[0060] The concentration of the N-substituted maleimide in the organic layer before the water washing step is preferably from 0.5 to 30% by mass, more preferably from 10 to 25% by mass, and further preferably from 20 to 25% by mass. The temperature at which the organic layer and the aqueous layer are mixed and washed may be 40°C or higher, preferably 40°C or higher and 80°C or lower, and more preferably 50°C or higher and 60°C or lower. The mass ratio of the aqueous layer to the organic layer is preferably 5% by mass or more and 300% by mass or less, more preferably 10% by mass or more and 200% by mass or less, and even more preferably 30% by mass or more and 100% by mass or less, assuming that the mass of the organic layer is 100% by mass. It is preferable that the concentration of the N-substituted maleimide in the organic layer, the liquid temperature during washing, and the mass ratio of the aqueous layer are within these ranges, since the reaction between the N-substituted maleimide and water does not easily proceed and the 2-amino-N-substituted succinimide is easily extracted into the aqueous layer.
[0061] When washing in a batch system, the reaction vessel used may be made of stainless steel or glass-lined, or other reaction vessels may be used. The shape of the stirring blade is not particularly limited. Specific stirring blades that can be used include, for example, three-blade swept-back blades, four-blade paddle blades, four-blade inclined paddle blades, six-blade turbine blades, and anchor blades. In addition, Twin Star and Full Zone manufactured by Kobe Steel Eco-Solutions can be used. The stirring time is preferably 10 minutes or more and 120 minutes or less, more preferably 30 minutes or more and 60 minutes or less. The stirring speed is appropriately selected so that the mixture becomes turbulent and does not emulsify. When the stirring time and stirring speed are within these ranges, the stirring efficiency and the extraction efficiency of 2-amino-N-substituted succinimide into the aqueous layer are improved, and the 2-amino-N-substituted succinimide in the N-substituted maleimide can be further reduced, which is preferable.
[0062] When washing is carried out in a continuous manner, an empty tower, a packed tower, or a plate tower can be used, and a stationary mixer such as a static mixer or a rotary mixer such as a dynamic mixer can also be used. The contact time between the organic layer and the aqueous layer is preferably set to 1 second to 60 minutes, more preferably 30 seconds to 10 minutes, since the reaction between the N-substituted maleimide and water does not proceed easily and the 2-amino-N-substituted succinimide is easily extracted into the aqueous layer.
[0063] In the dehydration step, the organic layer is placed in a reaction vessel and heated under reduced pressure to remove water. There are no particular limitations on the pressure and temperature as long as the solvent and water used form an azeotropic composition. The water content in the organic layer after the dehydration step is preferably 100 ppm by mass or less, assuming that the mass of the organic layer is 100% by mass. If the water content after the dehydration step is in this range, it is possible to suppress color deterioration due to water during polymerization of the methacrylic resin, and also to reduce the amount of solvent distilled off together with water, which is preferable from the viewpoint of cost. The organic layer containing the N-substituted maleimide obtained in the dehydration step may be used in the polymerization step as an N-substituted maleimide solution, or an N-substituted maleimide solution whose concentration has been adjusted in the concentration adjustment step may be used in the polymerization step.
[0064] In the concentration adjustment step, for example, the organic layer of the N-substituted maleimide obtained in the dehydration step or the like may be diluted with the water-insoluble organic solvent. The water-insoluble organic solvent used in the concentration adjustment step is preferably the same as the water-insoluble organic solvent used in the water-washing step.
[0065] The N-substituted maleimide solution obtained in the pretreatment step is preferably a solution in the water-insoluble organic solvent (organic layer). The N-substituted maleimide solution obtained in the pretreatment step preferably has a mass ratio of 2-amino-N-substituted succinimide contained in the N-substituted maleimide solution of 5 ppm by mass or less, more preferably 0.1 ppm by mass or more and 1 ppm by mass or less, relative to 100% by mass of N-substituted maleimide contained in the N-substituted maleimide solution. The water content in the N-substituted maleimide solution obtained in the above pretreatment step is preferably 200 ppm by mass or less, and more preferably 100 to 200 ppm by mass, relative to 100% by mass of the N-substituted maleimide solution. The mass ratio of the N-substituted maleimide contained in the N-substituted maleimide solution obtained in the above pretreatment step is preferably 5 to 30 mass %, more preferably 5 to 25 mass %, relative to 100 mass % of the N-substituted maleimide solution. When it is within this range, the N-substituted maleimide is less likely to precipitate and can be transported as a homogeneous solution, which is preferable.
[0066] When a plurality of types of N-substituted maleimide solutions are used in the polymerization step, it is preferable that a mixture of the plurality of types of N-substituted maleimide solutions satisfies the above-mentioned mass ratio of the 2-amino-N-substituted succinimide, the above-mentioned water content, and / or the mass ratio of the N-substituted maleimide, and it is more preferable that each N-substituted maleimide solution satisfies the above-mentioned mass ratio of the 2-amino-N-substituted succinimide, the above-mentioned water content, and / or the mass ratio of the N-substituted maleimide. By employing the above-mentioned water-washing step and dehydration step of the N-substituted maleimide, it is possible to reduce the amount of 2-amino-N-substituted succinimide having fluorescent properties and to remove moisture that causes deterioration of the color tone of the methacrylic resin, and thus it is possible to obtain a methacrylic resin and a composition of said resin having good color tone even in lenses with long optical paths, which is preferable. In the polymerization step, the N-substituted maleimide solution obtained in the pretreatment step may be mixed with a methacrylic acid ester monomer, any other monomer, a polymerization initiator, a polymerization solvent, a chain transfer agent, etc. to prepare a monomer mixture liquid, which may then be used in the polymerization.
[0067] (2) Reduction of unreacted N-substituted maleimide at the end of polymerization The present inventors have found that if unreacted N-substituted maleimide is present at the end of polymerization of a methacrylic resin, a low-molecular-weight fluorescent reaction by-product containing N-substituted maleimide as a structural unit may be generated in a heated volatilizer, for example, although the detailed mechanism is unclear.
[0068] In order to control the content of the fluorescent substance in the methacrylic resin and the resulting resin lens within the above-mentioned range, the total mass of unreacted N-substituted maleimide remaining after completion of polymerization is preferably 1,000 ppm by mass or less, and more preferably 10 ppm by mass or more and 500 ppm by mass or less, relative to 100% by mass of the polymerization solution at the end of polymerization. Furthermore, when an N-arylmaleimide such as N-phenylmaleimide is used as the N-substituted maleimide, the total mass of unreacted N-arylmaleimides remaining after the completion of polymerization is preferably 500 ppm by mass or less, more preferably 10 ppm by mass or more and 500 ppm by mass or less, and even more preferably 10 ppm by mass or more and 50 ppm by mass or less, relative to 100% by mass of the polymerization solution at the time of the completion of polymerization. When the content is within these ranges, the content of the fluorescent substance in the methacrylic resin and the resulting resin lens can be suppressed within the above-mentioned ranges, which is preferable. In addition, in order to make the amount of unreacted N-substituted maleimide less than 10 ppm by mass, it is necessary to increase the polymerization temperature or the amount of polymerization initiator, which is undesirable because it increases the amount of thermally denatured maleimide and active radicals, causing deterioration in the color tone of the methacrylic resin.
[0069] As a means for controlling the amount of unreacted N-substituted maleimide after the end of polymerization to the above range, a semi-batch polymerization method can be mentioned. In the semi-batch polymerization method, in the polymerization step, it is preferable to additionally add 5 to 35% by mass of methacrylic acid ester monomer, assuming that the total mass of all monomers provided to the polymerization (e.g., methacrylic acid ester, N-substituted maleimide, and any other monomer) is 100% by mass, after 30 minutes from the start of addition of the polymerization initiator. In other words, it is preferable to charge 65 to 95% by mass of the total mass of all monomers provided to the polymerization (100% by mass) into the reactor before adding the polymerization initiator, and additionally add the remaining 5 to 35% by mass of the methacrylic acid ester monomer, after 30 minutes from the start of addition of the polymerization initiator. The amount of methacrylic acid ester monomer to be additionally added is more preferably 10 to 30% by mass, assuming that the total mass of all monomers provided to the polymerization is 100% by mass. When the amount of the additionally added methacrylic acid ester monomer is within the above range, the unreacted N-substituted maleimide reacts with the additionally added methacrylic acid ester monomer, and the amount of unreacted N-substituted maleimide after completion of polymerization can be controlled within the above range, which is preferable.
[0070] The start time of additional addition of the monomer, the speed of additional addition, etc. may be appropriately selected depending on the polymerization conversion rate. Furthermore, in addition to the methacrylic acid ester monomer, a monomer mixture containing an N-substituted maleimide monomer and other monomers may be additionally added within a range that does not impair the effects of the present invention or the reduction of the amount of unreacted N-substituted maleimide. By employing the semi-batch polymerization method as described above, it is possible to reduce the amount of unreacted N-substituted maleimide monomer at the latter stage of polymerization and minimize the production of fluorescent substances in the devolatilization step, and it is therefore preferable to obtain a methacrylic resin and a composition of said resin having good color tone even in lenses with long optical paths.
[0071] Hereinafter, as an example of a method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, a case where the resin is produced by radical polymerization in a semi-batch system using a solution polymerization method will be specifically described.
[0072] In the semi-batch polymerization method, it is preferable to additionally add 5 to 35% by mass of the methacrylic acid ester monomer, based on the total mass of all monomers (methacrylic acid ester, N-substituted maleimide, and any other monomers) to be polymerized, 30 minutes or more after the start of the addition of the polymerization initiator. In other words, it is preferable to charge 65 to 95% by mass of the total mass of all monomers to be polymerized, 100% by mass, into the reactor before the start of polymerization, and then additionally add the remaining 5 to 35% by mass of the methacrylic acid ester monomer 30 minutes or more after the start of the addition of the polymerization initiator. The amount of the methacrylic acid ester monomer to be additionally added is more preferably 10 to 30% by mass, with the total mass of all the monomers to be supplied to the polymerization being 100% by mass.
[0073] The start time of additional addition of the monomer, the speed of additional addition, etc. may be appropriately selected depending on the polymerization conversion rate. Furthermore, in addition to the methacrylic acid ester monomer, a monomer mixture containing the N-substituted maleimide monomer and other monomers may be additionally added within a range that does not impair the effects of the present invention or the increase in the conversion rate of the N-substituted maleimide monomer.
[0074] By employing the semi-batch polymerization method as described above, it is possible to increase the conversion rate of the N-substituted maleimide monomer at the latter stage of the polymerization, reduce the content of the fluorescent substance, provide a lens with a long optical path length with excellent light transmittance, and make it easy to control the molecular weight distribution of the resulting polymer. In particular, it is preferable to obtain a resin and a composition of said resin having flowability suitable for injection molding.
[0075] The polymerization solvent to be used is not particularly limited as long as it can increase the solubility of the maleimide copolymer obtained by polymerization and can appropriately maintain the viscosity of the reaction solution for the purpose of preventing gelation, etc. Specific examples of the polymerization solvent that can be used include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone. These may be used alone or in combination of two or more. Furthermore, alcohols such as methanol, ethanol, and isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit dissolution of the polymerization product during polymerization.
[0076] The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds and the amount is easily removable without causing precipitation of the copolymer or monomers used during production, but for example, when the total amount of the monomers to be blended is taken as 100% by mass, the amount is preferably 10 to 200% by mass, more preferably 25 to 150% by mass, even more preferably 40 to 100% by mass, and even more preferably 50 to 100% by mass. In the present embodiment, a method of polymerization in which the amount of solvent during polymerization is within a range of 100 mass% or less when the total amount of the monomers to be blended is taken as 100 mass% can also be preferably used while appropriately changing the solvent concentration during polymerization. More specifically, an example of the method is to blend 40 to 60 mass% in the early stage of polymerization, blend the remaining 60 to 40 mass% during the polymerization, and finally blend the amount of the solvent in a range of 100 mass% or less when the total amount of the blended monomers is 100 mass%. By employing this method, it is possible to increase the polymerization conversion rate, and further to control the molecular weight distribution, and it is possible to obtain a resin and a resin composition that have excellent injection moldability, a reduced content of fluorescent substances, and good color tone even when a lens with a long optical path length is prepared. This is therefore preferable.
[0077] In solution polymerization, it is important to reduce the dissolved oxygen concentration in the polymerization solution as much as possible, and for example, the dissolved oxygen concentration is preferably 10 ppm or less. The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter DO meter B-505 (manufactured by Iijima Electronics Co., Ltd.). Methods for reducing the dissolved oxygen concentration can be appropriately selected from a method of bubbling an inert gas into the polymerization solution, a method of repeatedly pressurizing a container containing the polymerization solution to about 0.2 MPa with an inert gas before polymerization and then releasing the pressure, a method of passing an inert gas through a container containing the polymerization solution, and the like.
[0078] The polymerization temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but is preferably 70 to 180° C., more preferably 80 to 160° C., even more preferably 90 to 150° C., and even more preferably 100 to 150° C. From the viewpoint of productivity, it is preferable to set the temperature at 70° C. or higher, and it is preferable to set the temperature at 180° C. or lower in order to suppress side reactions during polymerization and obtain a polymer with the desired molecular weight and quality.
[0079] The polymerization time is not particularly limited as long as it is a time that can obtain a required degree of polymerization at a required conversion rate, but from the viewpoint of productivity, etc., it is preferably 2 to 15 hours, more preferably 3 to 12 hours, and even more preferably 4 to 10 hours.
[0080] As the polymerization initiator, any initiator generally used in radical polymerization can be used. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butylperoxyisopropyl carbonate, t-amylperoxy-2-ethylhexanoate, t-amylperoxyisononanoate, and 1,1-di(t-butylperoxy)cyclohexane; and azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate. These may be used alone or in combination of two or more. The amount of the polymerization initiator added may be 0.01 to 1% by mass, and preferably 0.05 to 0.5% by mass, assuming that the total amount of the monomers used in the polymerization is 100% by mass. The method of adding the polymerization initiator is not particularly limited as long as it is not a constant addition rate but a variable addition rate according to the monomer concentration remaining in the polymerization solution, and may be added continuously or intermittently. When the polymerization initiator is added intermittently, the amount added per unit time is not considered for the time when the polymerization initiator is not added.
[0081] In this embodiment, it is preferable to appropriately select the type and amount of the polymerization initiator, the polymerization temperature, and the like so that the ratio of the total amount of radicals generated from the polymerization initiator to the total amount of unreacted monomers remaining in the reaction system is always equal to or less than a certain value. By employing these methods, it is possible to suppress the production of oligomers and low molecular weight materials in the later stages of polymerization, and to prevent overheating during polymerization, thereby ensuring the stability of the polymerization.
[0082] During the polymerization reaction, a chain transfer agent may be added as necessary. As the chain transfer agent, any chain transfer agent used in general radical polymerization can be used, and examples thereof include mercaptan compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, etc.; halogen compounds such as carbon tetrachloride, methylene chloride, bromoform, etc.; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene, etc.; and the like. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent added may be 0.01 to 1% by mass, and preferably 0.05 to 0.5% by mass, when the total amount of the monomers used in the polymerization is taken as 100% by mass.
[0083] As a method for recovering a polymer from a polymerization solution obtained by solution polymerization, there is a method in which the polymerization solvent and unreacted monomers are separated through a process called a devolatilization process, and the polymerization product is recovered. Here, the devolatilization process refers to a process in which volatile matters such as the polymerization solvent, residual monomers, and reaction by-products are removed under heating and reduced pressure conditions. In this embodiment, it is preferable to control the content of unreacted N-substituted maleimide monomer contained in the polymerization solution containing the methacrylic resin to be subjected to the volatilization step to a certain concentration or less. Details are as described above in "(2) Reduction of unreacted N-substituted maleimide at the end of polymerization". In addition to the above-mentioned methods, for example, in order to increase the monomer conversion rate, a method of polymerization by lengthening the polymerization time as much as possible or changing the addition rate of the polymerization initiator according to the concentration of unreacted monomer in the polymerization solution; a method of polymerization while appropriately changing the solvent concentration during polymerization; a method of additionally adding another monomer that is highly reactive with the N-substituted maleimide monomer remaining in the latter half of polymerization; a method of adding a compound that is highly reactive with N-substituted maleimide, such as α-terpinene, at the end of polymerization, and the like can also be used.
[0084] -Remaining amount of N-substituted maleimide monomer- The amount of N-substituted maleimide monomer remaining in a polymerization solution containing a methacrylic resin can be determined, for example, by collecting and weighing a portion of the polymerization solution, dissolving this sample in chloroform to prepare a 5% by mass solution, adding n-decane as an internal standard substance, and measuring the concentration of the N-substituted maleimide monomer remaining in the sample using gas chromatography (Shimadzu Corporation GC-2010). More specific measurement conditions can be those described in the Examples below.
[0085] (3) Devolatilization method with reduced shear The volatilization step is preferably performed using a volatilization device mainly composed of a heat exchanger and a reduced pressure vessel, and having no rotating part in its structure. By not providing a rotating part, shear during volatilization can be reduced, and a resin with lower fluorescent light emission can be obtained. Specifically, a volatilizing apparatus can be used which is composed of a volatilizing tank having a reduced pressure vessel with a heat exchanger disposed on the upper portion thereof and a size allowing volatilization, to which a reduced pressure unit is attached, and a discharge device such as a gear pump for discharging the polymer after volatilization. The volatilizer preheats the polymerization solution by feeding it to a heated heat exchanger, such as a multi-tube heat exchanger, a plate fin heat exchanger, or a flat plate heat exchanger having a flat plate flow path and a heater, which is disposed above the reduced pressure vessel, and then supplies it to a volatilizer tank under heating and reduced pressure to separate and remove the polymerization solvent, unreacted raw material mixture, polymerization by-products, and the like, and the polymer. By using a volatilizer without a rotating part as described above, it is possible to suppress low molecular weight, fluorescent reaction by-products derived from unreacted N-substituted maleimide, and it is preferable because the fluorescence intensity (content of fluorescent substance) in the methacrylic resin and the obtained resin lens can be controlled within a predetermined range. It is also preferable because it is possible to obtain a methacrylic resin with a good color tone.
[0086] Examples of the device having a rotating part include thin film evaporators such as Wiplen and Exeva manufactured by Kobelco Eco-Solutions Co., Ltd., and Contra and tilted blade Contra manufactured by Hitachi, Ltd.; and vented extruders.
[0087] In the devolatilization step in this embodiment, the shear rate applied to the polymerization solution is 20 s -1 It is preferable to set it to 10s or less. -1 It is more preferable to set it to 0.1 s or less. -1 More than 10s -1 It is more preferable to carry out the process at a shear rate of 0.1 s -1 By setting the temperature at 20 s or more, the flow of the molten resin does not become too slow, and deterioration of color tone due to an increase in residence time can be suppressed. -1 By setting the above ratio as below, it is possible to suppress the generation of fluorescent reaction by-products due to shear. Here, for example, the shear rate γ in the extruder is calculated by the following formula. γ = (π × D × N) / H (In the formula, D represents the screw diameter (m), N represents the screw rotation speed per second, and H represents the screw groove depth (m).) In the case of a flat plate type flow channel, the shear rate γ is calculated by the following formula. γ = (6 × Q) / (w × h 2 ) (Where, Q is the volumetric flow rate (m 3 / s), w is the width of the flat channel (m), and h is the distance between the flat plates (m).
[0088] In this embodiment, the heat exchanger disposed in the upper part of the reduced pressure vessel is preferably a flat plate type heat exchanger having a flat plate type flow passage and a heater, and more preferably a flat plate type heat exchanger having a heater and a flat plate type flow passage having a laminated structure with a plurality of slit-shaped flow passages having rectangular cross sections on the same plane.
[0089] The polymerization solution fed to the volatilizer is sent from the center of the heat exchanger to the slit-shaped flow passage and heated. The heated polymerization solution is fed from the slit-shaped flow passage into a reduced pressure vessel integrated with the heat exchanger under reduced pressure and flash evaporated. Such a devolatilization method is also called flash devolatilization, and in the present invention, it will hereinafter also be referred to as flash devolatilization.
[0090] It is also possible to employ a method in which two or more of the above-mentioned volatilizing apparatuses are installed in series to perform volatilization in two or more stages.
[0091] The temperature range of the heat exchanger attached to the volatilization apparatus may be 100°C or higher and 300°C or lower, preferably a temperature of the glass transition temperature (Tg) of the methacrylic resin + 100°C to Tg + 160°C, more preferably a temperature of Tg + 110°C to Tg + 150°C. The temperature range of the heated and kept warm volatilization tank may be 100°C or higher and 300°C or lower, preferably a temperature of Tg + 100°C to Tg + 160°C, more preferably a temperature of Tg + 110°C to Tg + 150°C. When the temperature of the heat exchanger and the volatilization tank is within this range, the thermal denaturation of the remaining 2-amino-N-substituted succinimide can be suppressed, and the generation of fluorescent substances can be suppressed, which is preferable. In addition, it is effective in preventing the amount of remaining volatile matter from increasing, and is preferable because the thermal stability and product quality of the obtained methacrylic resin are improved.
[0092] The degree of vacuum in the volatilizing tank may be in the range of 5 to 300 Torr, and preferably in the range of 10 to 200 Torr. When the degree of vacuum is 300 Torr or less, the unreacted monomer or the mixture of the unreacted monomer and the polymerization solvent can be efficiently separated and removed, and the thermal stability and quality of the obtained thermoplastic copolymer are not deteriorated. When the degree of vacuum is 5 Torr or more, industrial implementation is easier.
[0093] The average residence time in the devolatilization tank is 5 to 60 minutes, preferably 5 to 45 minutes. When the average residence time is within this range, devolatilization can be performed efficiently and coloration and decomposition of the polymer due to thermal denaturation can be suppressed, which is preferable.
[0094] The polymer recovered through the devolatilization step is processed into pellets in a step called a granulation step. In the granulation process, the molten resin is extruded in a strand shape using at least one type of discharge granulation device selected from a gear pump having a multi-hole die as an auxiliary equipment, a single screw extruder, a twin screw extruder, etc., and processed into pellets using a cold cut method, an air hot cut method, an underwater strand cut method, or an underwater cut method. From the viewpoint of suppressing the generation of fluorescent reaction by-products due to shear, it is preferable to select a conveying device with a low shear rate without using an extruder.
[0095] In this embodiment, in order to obtain a highly controlled resin composition, it is preferable to adopt a granulation method that can quickly cool and solidify the resin composition in a molten state at high temperature while minimizing contact with air as much as possible. In this case, it is more preferable to carry out granulation under conditions in which the molten resin temperature is as low as possible, the residence time from the multi-hole die outlet to the cooling water surface is as short as possible, and the cooling water temperature is as high as possible. For example, the molten resin temperature is preferably 220 to 280°C, and more preferably 230 to 270°C, the residence time from the multi-hole die outlet to the cooling water surface is preferably within 5 seconds, and more preferably within 3 seconds, and the cooling water temperature is preferably in the range of 30 to 80°C, and more preferably 40 to 60°C.
[0096] By carrying out the process within these ranges of the molten resin temperature and the cooling water temperature, it is possible to obtain a methacrylic resin and a composition thereof which are less colored and have a low moisture content, which is preferable.
[0097] The smaller the content of the monomer remaining in the methacrylic resin after the devolatilization step, the better from the viewpoint of thermal stability and product quality. Specifically, the content of the methacrylic acid ester monomer is preferably 3000 mass ppm or less, more preferably 2000 mass ppm or less. The content of the N-substituted maleimide monomer is preferably 200 mass ppm or less in total, more preferably 100 mass ppm or less. The content of the residual polymerization solvent is preferably 500 ppm by mass or less, and more preferably 300 ppm by mass or less.
[0098] -Method for producing methacrylic resin containing glutarimide structural unit- Examples of a method for producing a methacrylic resin having a glutarimide structural unit in the main chain include a bulk polymerization method, a solution polymerization method, a suspension polymerization method, a precipitation polymerization method, and an emulsion polymerization method. Of these, the suspension polymerization method, the bulk polymerization method, and the solution polymerization method are preferred, and the solution polymerization method is more preferred. In the production method of the present embodiment, any of a batch polymerization method, a semi-batch polymerization method, and a continuous polymerization method can be used as the polymerization method. In the production method of the present embodiment, it is preferable to polymerize the monomers by radical polymerization.
[0099] Methacrylic resins having glutarimide structural units in the main chain are, for example, methacrylic resins having glutarimide structural units described in JP 2006-249202 A, JP 2007-009182 A, JP 2007-009191 A, JP 2011-186482 A, WO 2012 / 114718 A, and the like, and can be formed by the methods described in these publications. Hereinafter, as an example of a method for producing a methacrylic resin having a glutarimide structural unit, a batch-type radical polymerization method using a solution polymerization method will be specifically described.
[0100] First, a (meth)acrylic acid ester such as methyl methacrylate is polymerized to produce a (meth)acrylic acid ester polymer. When an aromatic vinyl unit is to be contained in a methacrylic resin having a glutarimide structural unit, a (meth)acrylic acid ester and an aromatic vinyl (e.g., styrene) are copolymerized to produce a (meth)acrylic acid ester-aromatic vinyl copolymer.
[0101] Examples of the solvent used in the polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and the like. These solvents may be used alone or in combination of two or more kinds. The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds and the amount can be easily removed without causing precipitation of the copolymer or monomers used during production, but for example, when the total amount of the monomers to be blended is taken as 100 mass%, the amount is preferably 10 to 200 mass%, more preferably 25 to 200 mass%, even more preferably 50 to 200 mass%, and even more preferably 50 to 150 mass%.
[0102] The polymerization temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but is preferably 50 to 200° C., more preferably 80 to 200° C., even more preferably 90 to 150° C., even more preferably 100 to 140° C., and even more preferably 100 to 130° C. From the viewpoint of productivity, it is preferably 70° C. or higher, and is preferably 180° C. or lower in order to suppress side reactions during polymerization and to obtain a polymer with the desired molecular weight and quality. The polymerization time is not particularly limited as long as the desired conversion rate is achieved, but may be extended from the viewpoint of productivity, etc. From this viewpoint, the time is preferably 0.5 to 15 hours, more preferably 2 to 12 hours, and further preferably 1.5 to 2.5 hours. The period is preferably 4 to 10 hours.
[0103] During the polymerization reaction, a polymerization initiator or a chain transfer agent may be added as necessary.
[0104] The polymerization initiator is not particularly limited, but for example, the polymerization initiators disclosed in the method for preparing the methacrylic resin having a structural unit derived from the N-substituted maleimide monomer can be used. These polymerization initiators may be used alone or in combination of two or more kinds. These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress. The amount of the polymerization initiator added may be appropriately set depending on the combination of monomers, reaction conditions, etc., and is not particularly limited. When the total amount of the monomers used in the polymerization is taken as 100% by mass, the amount may be 0.01 to 1% by mass, and preferably 0.05 to 0.5% by mass.
[0105] As the chain transfer agent, a chain transfer agent used in general radical polymerization can be used, for example, the chain transfer agents disclosed in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent to be added is not particularly limited as long as it is within a range in which a desired degree of polymerization can be obtained under the polymerization conditions used, but is preferably 0.01 to 1 mass %, and more preferably 0.05 to 0.5 mass %, when the total amount of the monomers used in the polymerization is taken as 100 mass %.
[0106] In the polymerization step, a suitable method for adding a polymerization initiator and a chain transfer agent may be, for example, the method described in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer. The dissolved oxygen concentration in the polymerization solution may be, for example, the value disclosed in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer.
[0107] Next, the (meth)acrylic acid ester polymer or the methacrylic acid ester-aromatic vinyl copolymer is reacted with an imidizing agent to carry out an imidization reaction (imidization step), thereby producing a methacrylic resin having a glutarimide structural unit.
[0108] The imidizing agent is not particularly limited as long as it can generate the glutarimide structural unit represented by the general formula (3) above. Specifically, the imidizing agent may be ammonia or a primary amine. Examples of the primary amine include aliphatic hydrocarbon group-containing primary amines such as methylamine, ethylamine, n-propylamine, i-propylamine, n-butylamine, i-butylamine, tert-butylamine, and n-hexylamine; alicyclic hydrocarbon group-containing primary amines such as cyclohexylamine; and the like. Of the above imidizing agents, ammonia, methylamine and cyclohexylamine are preferred from the standpoint of cost and physical properties, with methylamine being particularly preferred.
[0109] In this imidization step, the content of glutarimide structural units in the resulting methacrylic resin having glutarimide structural units can be adjusted by adjusting the ratio of the imidization agent added.
[0110] The method for carrying out the imidization reaction is not particularly limited, and a conventionally known method can be used. For example, the imidization reaction can be carried out using an extruder or a batch-type reaction tank.
[0111] The extruder is not particularly limited, but for example, a single screw extruder, a twin screw extruder, a multi-screw extruder, etc. can be used. Among these, it is preferable to use a twin-screw extruder, which can promote mixing of the raw material polymer and the imidizing agent. Examples of twin-screw extruders include non-intermeshing co-rotating, intermeshing co-rotating, non-intermeshing counter-rotating, and intermeshing counter-rotating. The above-mentioned extruders may be used alone or in combination of a plurality of extruders connected in series. It is particularly preferable to equip the extruder to be used with a vent port capable of reducing the pressure to below atmospheric pressure, since this makes it possible to remove by-products of the reaction such as the imidizing agent, methanol, and the like, or monomers.
[0112] In producing a methacrylic resin having a glutarimide structural unit, in addition to the above-mentioned imidization step, an esterification step of treating the carboxyl group of the resin with an esterification agent such as dimethyl carbonate can be included. In this case, a catalyst such as trimethylamine, triethylamine, or tributylamine can also be used in combination for the treatment. The esterification step can be carried out, for example, by using an extruder or a batch reaction tank, in the same manner as in the imidization step. For the purpose of removing excess esterifying agent, by-products such as methanol, or monomers, the apparatus used is preferably equipped with a vent port capable of reducing the pressure to atmospheric pressure or below.
[0113] The methacrylic resin that has been subjected to the imidization step and, if necessary, the esterification step is melted and extruded in the form of strands from an extruder equipped with a multi-hole die, and processed into pellets by a cold cut method, an in-air hot cut method, an underwater strand cut method, an underwater cut method, or the like. In order to reduce the number of foreign matters in the resin, it is also preferable to use a method in which the methacrylic resin is dissolved in an organic solvent such as toluene, methyl ethyl ketone, or methylene chloride, the obtained methacrylic resin solution is filtered, and then the organic solvent is removed.
[0114] From the viewpoint of reducing the fluorescence intensity (content of the fluorescent substance), it is preferable to imidize the polymer solution after the completion of the polymerization in a batch reaction tank without using a twin-screw extruder that is subjected to a shearing force. The imidization reaction is preferably carried out at 130 to 250° C., more preferably at 150 to 230° C., and even more preferably at 170 to 190° C. The reaction time is preferably 10 minutes to 5 hours, and more preferably 30 minutes to 2 hours. After the imidization step, an esterification step may be carried out as necessary, and then the volatilization is carried out by the volatilization method with reduced shear (3) described in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, followed by pelletization, which is preferable from the viewpoint of reducing fluorescence intensity.
[0115] -Method for producing methacrylic resin containing lactone ring structural unit- As a method for producing a methacrylic resin having a lactone ring structural unit in the main chain, a method in which a lactone ring structure is formed by a cyclization reaction after polymerization is used. In order to promote the cyclization reaction, however, it is preferable to polymerize a monomer by radical polymerization using a solution polymerization method using a solvent. In the production method of the present embodiment, any of a batch polymerization method, a semi-batch polymerization method, and a continuous polymerization method can be used as the polymerization method. Methacrylic resins having a lactone ring structural unit in the main chain can be formed by the methods described in, for example, JP-A Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.
[0116] As an example of a method for producing a methacrylic resin having a lactone ring structural unit, a batchwise radical polymerization method using a solution polymerization method will be specifically described below. As a method for producing a methacrylic resin having a lactone ring structural unit, a method of forming a lactone ring structure by a cyclization reaction after polymerization is used. In order to promote the cyclization reaction, solution polymerization using a solvent is preferred.
[0117] Examples of the solvent used in the polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and the like. These solvents may be used alone or in combination of two or more kinds.
[0118] The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds and gelation can be suppressed. For example, the amount of the solvent is preferably 50 to 200% by mass, and more preferably 100 to 200% by mass, assuming that the total amount of the monomers to be blended is 100% by mass.
[0119] In order to sufficiently suppress gelation of the polymerization solution and promote the cyclization reaction after polymerization, it is preferable to carry out the polymerization so that the concentration of the produced polymer in the reaction mixture obtained after polymerization is 50% by mass or less. It is also preferable to control the concentration to 50% by mass or less by adding a polymerization solvent to the reaction mixture as appropriate.
[0120] The method for appropriately adding the polymerization solvent to the reaction mixture is not particularly limited, and for example, the polymerization solvent may be added continuously or intermittently. The polymerization solvent to be added may be a single solvent or a mixed solvent of two or more solvents. The polymerization temperature is not particularly limited as long as the polymerization proceeds at the temperature, but is preferably 50 to 200°C, more preferably 80 to 180°C, from the viewpoint of productivity. The polymerization time is not particularly limited as long as the target conversion rate is achieved, but from the viewpoint of productivity, etc., it is preferably 0.5 to 10 hours, more preferably 1 to 8 hours.
[0121] During the polymerization reaction, a polymerization initiator or a chain transfer agent may be added, if necessary. The polymerization initiator is not particularly limited, but for example, the polymerization initiators disclosed in the method for preparing the methacrylic resin having a structural unit derived from the N-substituted maleimide monomer can be used. These polymerization initiators may be used alone or in combination of two or more kinds. These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress. The amount of the polymerization initiator to be added may be appropriately set depending on the combination of monomers, reaction conditions, etc., and is not particularly limited. When the total amount of the monomers used in the polymerization is taken as 100% by mass, the amount may be 0.05 to 1% by mass.
[0122] As the chain transfer agent, a chain transfer agent used in general radical polymerization can be used, for example, the chain transfer agents disclosed in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent to be added is not particularly limited as long as the desired degree of polymerization is obtained under the polymerization conditions used, but is preferably 0.05 to 1 mass % when the total amount of the monomers to be used in the polymerization is taken as 100 mass %.
[0123] In the polymerization step, a suitable method for adding a polymerization initiator and a chain transfer agent may be, for example, the method described in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer.
[0124] The dissolved oxygen concentration in the polymerization solution may be, for example, the value disclosed in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer.
[0125] The methacrylic resin having a lactone ring structural unit in this embodiment can be obtained by carrying out a cyclization reaction after the completion of the polymerization reaction. Therefore, it is preferable to subject the polymerization reaction liquid to the lactone cyclization reaction while still containing the solvent, without removing the polymerization solvent from the polymerization reaction liquid. When the copolymer obtained by polymerization is heated, a cyclization condensation reaction occurs between the hydroxyl groups (hydroxyl groups) and ester groups present in the molecular chain of the copolymer, forming a lactone ring structure. In the heat treatment for forming the lactone ring structure, a reaction apparatus equipped with a vacuum device or a volatilizing device, an extruder equipped with a volatilizing device, or the like can be used to remove alcohol that may be by-produced by the cyclocondensation.
[0126] When forming the lactone ring structure, a heat treatment may be carried out using a cyclization condensation catalyst, if necessary, in order to promote the cyclization condensation reaction. Specific examples of the cyclization condensation catalyst include monoalkyl phosphite, dialkyl ester, or triester phosphite, such as methyl phosphite, ethyl phosphite, phenyl phosphite, dimethyl phosphite, diethyl phosphite, diphenyl phosphite, trimethyl phosphite, and triethyl phosphite; monoalkyl phosphate, dialkyl ester, or trialkyl ester phosphate, such as methyl phosphate, ethyl phosphate, 2-ethylhexyl phosphate, octyl phosphate, isodecyl phosphate, lauryl phosphate, stearyl phosphate, isostearyl phosphate, dimethyl phosphate, diethyl phosphate, di-2-ethylhexyl phosphate, diisodecyl phosphate, dilauryl phosphate, distearyl phosphate, diisostearyl phosphate, trimethyl phosphate, triethyl phosphate, triisodecyl phosphate, trilauryl phosphate, tristearyl phosphate, and triisostearyl phosphate; and organic zinc compounds, such as zinc acetate, zinc propionate, and zinc octyl. These may be used alone or in combination of two or more.
[0127] The amount of the cyclization condensation catalyst used is not particularly limited, but is, for example, preferably 0.01 to 3 mass %, and more preferably 0.05 to 1 mass %, relative to 100 mass % of the methacrylic resin. When the amount of the catalyst used is 0.01% by mass or more, it is effective in improving the reaction rate of the cyclization condensation reaction, and when the amount of the catalyst used is 3% by mass or less, it is effective in preventing the obtained polymer from being discolored or from being crosslinked, which makes it difficult to melt mold the polymer.
[0128] The timing of adding the cyclization condensation catalyst is not particularly limited, and for example, it may be added at the beginning of the cyclization condensation reaction, or during the reaction, or it may be added at both times. When the cyclization condensation reaction is carried out in the presence of a solvent, devolatilization can also be carried out at the same time.
[0129] The apparatus used when the cyclocondensation reaction and the devolatilization step are carried out simultaneously is not particularly limited, but a devolatilization apparatus consisting of a heat exchanger and a devolatilization tank, an extruder equipped with a vent, or an apparatus in which a devolatilization apparatus and an extruder are arranged in series is preferable, and a twin-screw extruder equipped with a vent is more preferable. The vented twin-screw extruder used is preferably one having a plurality of vent ports.
[0130] When a vented extruder is used, the reaction temperature is preferably 150 to 350° C., more preferably 200 to 300° C. If the reaction temperature is less than 150° C., the cyclization condensation reaction may be insufficient, resulting in a large amount of residual volatile matter. Conversely, if the reaction temperature exceeds 350° C., the resulting polymer may become discolored or decomposed. When using a vented extruder, the degree of vacuum is preferably 10 to 500 Torr, more preferably 10 to 300 Torr. If the degree of vacuum exceeds 500 Torr, volatile matter may easily remain. Conversely, if the degree of vacuum is less than 10 Torr, industrial implementation may be difficult.
[0131] When the above cyclization condensation reaction is carried out, it is also preferred to add an alkaline earth metal and / or amphoteric metal salt of an organic acid during granulation for the purpose of deactivating the remaining cyclization condensation catalyst. Examples of the alkaline earth metal and / or amphoteric metal salt of an organic acid that can be used include calcium acetylacetate, calcium stearate, zinc acetate, zinc octoate, and zinc 2-ethylhexylate.
[0132] After the cyclocondensation reaction step, the methacrylic resin is melted and extruded in the form of strands from an extruder equipped with a multi-hole die, and processed into pellets by a cold cut method, an in-air hot cut method, an underwater strand cut method, or an underwater cut method. The lactonization for forming the lactone ring structural unit may be carried out after the production of the resin and before the production of the resin composition (described later), or may be carried out during the production of the resin composition, together with melt-kneading of the resin and components other than the resin.
[0133] From the viewpoint of reducing the fluorescence intensity (content of the fluorescent substance), it is preferable to lactone-cyclize the polymerization solution after the completion of the polymerization in a batch-type reaction tank and not to use a twin-screw extruder that is subjected to a shear force. After the lactone-cyclization step, it is preferable to pelletize after devolatilization by the devolatilization method with reduced shear (3) described in the above-mentioned method for preparing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, from the viewpoint of reducing the fluorescence intensity.
[0134] [Additives] The resin composition constituting the resin lens for head mounted displays of the present embodiment may contain various additives within ranges that do not significantly impair the effects of the present invention described above. The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins, softeners / plasticizers such as paraffinic process oil, naphthenic process oil, aromatic process oil, paraffin, organic polysiloxane, and mineral oil, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites, and phosphate esters, other additives, and mixtures thereof.
[0135] -Antioxidants- The resin composition constituting the resin lens for head mounted displays of the present embodiment preferably contains an antioxidant that suppresses deterioration and coloring during molding or use. The antioxidant includes, but is not limited to, hindered phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and the like. These antioxidants may be used alone or in combination of two or more. From the viewpoint of improving thermal stability and suppressing molding defects, it is preferable to use multiple types of heat stabilizers in combination. For example, it is preferable to use at least one selected from a phosphorus-based antioxidant and a sulfur-based antioxidant in combination with a hindered phenol-based antioxidant.
[0136] Examples of the hindered phenol-based antioxidant include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[ 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 ,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like. In particular, pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.
[0137] In addition, as the hindered phenol-based antioxidant as the antioxidant, a commercially available phenol-based antioxidant may be used. Examples of such commercially available phenol-based antioxidants include, but are not limited to, Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), and the like. 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), Adeka STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), Adeka STAB AO-80 (3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (Cyanox 1790, manufactured by Cytec), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer Examples of such compounds include GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), and Vitamin E (manufactured by Eisai). Among these commercially available phenolic antioxidants, Irganox 1010, Adeka STAB AO-60, Adeka STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin. These may be used alone or in combination of two or more.
[0138] Examples of the phosphorus-based antioxidant as the antioxidant include, but are not limited to, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, tetrakis(2,4-di-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methyl phenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, di-t-butyl-m-cresyl-phosphonite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like.
[0139] Furthermore, commercially available phosphorus-based antioxidants may be used as the phosphorus-based antioxidant. Examples of commercially available phosphorus-based antioxidants include, but are not limited to, Irgafos 168 (Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A, ADK STAB PEP-8, ADK STAB HP-10, ADK STAB HP-10, ADK STAB 2112, manufactured by ADEKA, ADK STAB 1178, manufactured by ADEKA, ADK STAB 1500, manufactured by ADEKA, Sandstab P-EPQ, manufactured by Clariant, Weston 618, manufactured by GE, Weston 619G, manufactured by GE, Ultranox 626, manufactured by GE, Sumilizer GP GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like. Among these commercially available phosphorus-based antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of using them in combination with various other antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred. These phosphorus-based antioxidants may be used alone or in combination of two or more kinds.
[0140] In addition, examples of the sulfur-based antioxidant as the antioxidant include, but are not limited to, 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1 ,3-diylbis[3-dodecylthio]propionate] (ADEKA STAB AO-412S, manufactured by ADEKA Corporation), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ChemiNox PLS, manufactured by Chemipro Chemical Co., Ltd.), and di(tridecyl) 3,3'-thiodipropionate (AO-503, manufactured by ADEKA Corporation). Among these commercially available sulfur antioxidants, ADK STAB AO-412S and Cheminox PLS are preferred from the viewpoints of the effect of imparting thermal stability to the resin, the effect of using them in combination with various antioxidants, and ease of handling. These sulfur-based antioxidants may be used alone or in combination of two or more kinds.
[0141] The content of the antioxidant may be any amount that provides the effect of improving thermal stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, still more preferably 0.8% by mass or less, still more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass, relative to 100% by mass of the methacrylic resin.
[0142] The timing of adding the antioxidant is not particularly limited, and examples thereof include a method of adding the antioxidant to a monomer solution before polymerization and then initiating polymerization, a method of adding the antioxidant to a polymer solution after polymerization and mixing it and then subjecting it to a devolatilization step, a method of adding the antioxidant to a molten polymer after devolatilization and then mixing it and then pelletizing it, a method of adding the antioxidant when the pellets after devolatilization and pelletization are melt-extruded again, etc. Among these, from the viewpoint of preventing thermal deterioration and coloration in the devolatilization step, it is preferable to add the antioxidant to a polymer solution after polymerization and mix it, add it before the devolatilization step, and then subject it to the devolatilization step.
[0143] -Hindered amine light stabilizer- The resin composition constituting the resin lens for head mounted displays of the present embodiment may contain a hindered amine-based light stabilizer. The hindered amine light stabilizer is not particularly limited, but is preferably a compound containing three or more ring structures. Here, the ring structure is preferably at least one selected from the group consisting of an aromatic ring, an aliphatic ring, an aromatic heterocycle, and a non-aromatic heterocycle, and when one compound has two or more ring structures, they may be the same or different from each other. Examples of the hindered amine light stabilizer include, but are not limited to, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, N ,N'-Bis(2,2,6,6-tetramethyl-4-piperidyl)-N,N'-diformylhexamethylenediamine, polycondensation product of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl -4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5 Examples of such compounds include reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Among these, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl} {(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], a reaction product of 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and a reaction product of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol are preferred. The content of the hindered amine light stabilizer may be any amount that provides the effect of improving light stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, still more preferably 0.8% by mass or less, still more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass, relative to 100% by mass of the methacrylic resin.
[0144] --Ultraviolet absorber-- The resin composition constituting the resin lens for a head mounted display of the present embodiment may contain an ultraviolet absorbing agent. The ultraviolet absorbent is not particularly limited, but is preferably an ultraviolet absorbent having a maximum absorption wavelength of 280 to 380 nm, and examples thereof include benzotriazole-based compounds, benzotriazine-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, benzoate-based compounds, phenol-based compounds, oxazole-based compounds, cyanoacrylate-based compounds, and benzoxazinone-based compounds. Benzotriazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1 ,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidylmethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 side chain and linear alkyl esters. Among these, benzotriazole-based compounds having a molecular weight of 400 or more are preferred, and examples of commercially available products include Kemisorb (registered trademark) 2792 (manufactured by Chemipro Chemicals), Adeka STAB (registered trademark) LA31 (manufactured by ADEKA Corporation), and Tinuvin (registered trademark) 234 (manufactured by BASF). Benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specific examples of the benzotriazine compounds include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl). )-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4 -diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy -4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4- propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,Examples of the tris(2-hydroxy-3-methyl-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine include 6-tris(2-hydroxy-3-methyl-4-methoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine. As the benzotriazine compound, commercially available products may be used, such as Kemisorb 102 (manufactured by Chemipro Chemicals), LA-F70 (manufactured by ADEKA Corporation), LA-46 (manufactured by ADEKA Corporation), TINUVIN 405 (manufactured by BASF), TINUVIN 460 (manufactured by BASF), TINUVIN 479 (manufactured by BASF), and TINUVIN 1577FF (manufactured by BASF). Among these, ultraviolet absorbers having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-s-triazine skeleton (where "alkyloxy" refers to a long-chain alkyloxy group such as octyloxy, nonyloxy, decyloxy, etc.) are more preferably used because of their high compatibility with acrylic resins and excellent ultraviolet absorption properties. As the ultraviolet absorber, from the viewpoints of compatibility with the resin and volatility upon heating, in particular, benzotriazole-based compounds and benzotriazine-based compounds having a molecular weight of 400 or more are preferred, and from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing, benzotriazine-based compounds are particularly preferred. The melting point (Tm) of the ultraviolet absorbent is preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 160° C. or higher. The above-mentioned ultraviolet absorber preferably has a weight loss rate of 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and even more preferably 5% or less when heated from 23°C to 260°C at a rate of 20°C / min. These ultraviolet absorbents may be used alone or in combination of two or more. By using two types of ultraviolet absorbents having different structures in combination, ultraviolet rays in a wide wavelength range can be absorbed. The content of the ultraviolet absorber is not particularly limited as long as it does not impair heat resistance, moist heat resistance, thermal stability, and moldability and exerts the effects of the present invention, but is preferably 0.1 to 5 mass% relative to 100 mass% of the methacrylic resin, more preferably 0.2 to 4 mass% or less, more preferably 0.25 to 3 mass%, and even more preferably 0.3 to 3 mass%. When it is within this range, an excellent balance of ultraviolet absorbing performance, moldability, etc. is achieved.
[0145] --Release agent-- The resin composition constituting the resin lens for head mounted displays of the present embodiment may contain a mold release agent. Examples of the mold release agent include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon-based lubricants, alcohol-based lubricants, polyalkylene glycols, carboxylates, and hydrocarbon paraffin-based mineral oils.
[0146] The fatty acid ester that can be used as the release agent is not particularly limited, and any of the conventionally known fatty acid esters can be used. Examples of fatty acid esters that can be used include ester compounds of fatty acids having 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, arachic acid, and behenic acid, with monohydric aliphatic alcohols, such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols, such as glycerin, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids, polybasic organic acids, and monohydric aliphatic alcohols or polyhydric aliphatic alcohols.
[0147] Examples of such fatty acid esters include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monopalmitate, glycerin dipalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin monooleate, glycerin dioleate, glycerin trioleate, and glycerin monolinoleate. , glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin di 12-hydroxystearate, glycerin tri 12-hydroxystearate, glycerin diacetomonostearate, glycerin citric acid fatty acid ester, pentaerythritol adipic acid stearate, partially saponified montanic acid ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate. These fatty acid esters can be used alone or in combination of two or more. Examples of commercially available products include the Rikemal series, Poem series, Rikestar series, and Rikemaster series manufactured by Riken Vitamin Co., Ltd., and the Excel series, Leodor series, Exepar series, and Coconard series manufactured by Kao Corporation, and more specific examples include Rikemal S-100, Rikemal H-100, Poem V-100, Rikemal B-100, Rikemal HC-100, Rikemal S-200, Poem B-200, Rikestar EW-200, Rikestar EW-400, Excel S-95, and Leodor MS-50.
[0148] The fatty acid amide is also not particularly limited, and any of the conventionally known fatty acid amides can be used. Examples of fatty acid amides include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; methylol amides such as methylol stearic acid amide and methylol behenic acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and ethylene bisstearic acid amide (ethylene bis saturated fatty acid bisamides such as ethylene bisstearylamide, ethylene bisisostearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipamide, and N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide; and aromatic bisamides such as m-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide. These fatty acid amides can be used alone or in combination of two or more. Examples of commercially available products include the Diamid series (manufactured by Nippon Kasei Co., Ltd.), the Amide series (manufactured by Nippon Kasei Co., Ltd.), the Nikka Amide series (manufactured by Nippon Kasei Co., Ltd.), the Methylol Amide series, the Bis Amide series, the Slipax series (manufactured by Nippon Kasei Co., Ltd.), the Kaowax series (manufactured by Kao Corporation), the Fatty Acid Amide series (manufactured by Kao Corporation), and ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industry Co., Ltd.).
[0149] The fatty acid metal salt refers to a metal salt of a higher fatty acid, and examples thereof include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, and lithium 12-hydroxystearate. Of these, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred because the resulting transparent resin composition has excellent processability and extremely excellent transparency. Examples of commercially available products include the SZ series, SC series, SM series, and SA series manufactured by Sakai Chemical Industry Co., Ltd. When the fatty acid metal salt is used, its content is preferably 0.2% by mass or less relative to 100% by mass of the resin composition, from the viewpoint of maintaining transparency.
[0150] The above-mentioned release agents may be used alone or in combination of two or more kinds.
[0151] The release agent to be used is preferably one having a decomposition onset temperature of 200° C. or higher. Here, the decomposition onset temperature can be measured based on the 1% mass loss temperature by TGA.
[0152] The content of the release agent may be an amount that can obtain the effect as a release agent, and if the content is excessive, problems such as bleed-out during processing and extrusion failure due to screw slippage may occur, so the content is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, even more preferably 0.8% by mass or less, still more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass, relative to 100% by mass of the methacrylic resin. When the release agent is added in the amount within the above range, the decrease in transparency due to the addition of the release agent is suppressed, and release failure during injection molding tends to be suppressed, so this is preferable.
[0153] -Other thermoplastic resins- The resin composition constituting the resin lens for head mounted displays of the present embodiment may contain thermoplastic resins other than methacrylic resins for the purpose of adjusting birefringence or improving flexibility without impairing the object of the present invention.
[0154] Other thermoplastic resins include, for example, polyacrylates such as polybutyl acrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene block copolymer; and further, for example, acrylic rubber particles having a 3-4 layer structure described in JP-A-59-202213, JP-A-63-27516, JP-A-51-129449, JP-A-52-56150, etc.; rubbery polymers disclosed in JP-B-60-17406 and JP-A-8-245854; methacrylic rubber-containing graft copolymer particles obtained by multistage polymerization described in WO 2014-002491; and the like. Among these, from the viewpoint of obtaining good optical properties and mechanical properties, rubber-containing graft copolymer particles having a graft portion on their surface layer made of a composition compatible with styrene-acrylonitrile copolymers and methacrylic resins containing a structural unit (X) having a ring structure in the main chain are preferred.
[0155] The average particle size of the above-mentioned acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, and more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the film obtained from the composition of this embodiment.
[0156] The content of the other thermoplastic resin is preferably 0 to 50% by mass, and more preferably 0 to 25% by mass, based on 100% by mass of the methacrylic resin.
[0157] [Method of producing resin composition] The method for producing the resin composition constituting the resin lens for head mounted display of the present embodiment is not particularly limited as long as a composition satisfying the requirements of the present invention can be obtained. For example, a method of kneading using a kneader such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer can be mentioned. Among them, kneading using an extruder is preferred in terms of productivity. The kneading temperature may be in accordance with the preferred processing temperature of the polymer constituting the methacrylic resin or the other resin to be mixed, and is roughly in the range of 140 to 300°C, preferably in the range of 180 to 280°C. In addition, it is preferable to provide a vent port in the extruder for the purpose of reducing volatile content.
[0158] Here, in the resin composition constituting the resin lens for head mounted displays of the present embodiment, the amount of remaining solvent (residual solvent amount) is preferably less than 1000 ppm by mass, more preferably less than 800 ppm by mass, and even more preferably less than 700 ppm by mass. Here, the remaining solvent refers to the polymerization solvent (excluding alcohols) used during polymerization and the solvent used when redissolving and dissolving the resin obtained by polymerization. Specific examples of the polymerization solvent include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; polar solvents such as dimethylformamide and 2-methylpyrrolidone; and the like. Examples of the solvent used for redissolution include toluene, methyl ethyl ketone, and methylene chloride.
[0159] The resin composition constituting the resin lens for head mounted displays of the present embodiment preferably has a residual alcohol amount (residual alcohol content) of less than 500 ppm by mass, more preferably less than 400 ppm by mass, and even more preferably less than 350 ppm by mass. The remaining alcohol herein refers to an alcohol by-produced in the cyclization condensation reaction, and specific examples thereof include aliphatic alcohols such as methanol, ethanol, and isopropanol.
[0160] The amount of the remaining solvent and the amount of the remaining alcohol can be measured by gas chromatography.
[0161] Whichever method is selected, it is preferable to prepare the composition after reducing oxygen and water as much as possible. For example, the dissolved oxygen concentration in the polymerization solution in solution polymerization is preferably less than 300 ppm in the polymerization step, and in a preparation method using an extruder or the like, the oxygen concentration in the extruder is preferably less than 1% by volume, more preferably less than 0.8% by volume. The water content of the methacrylic resin is preferably adjusted to 1000 ppm by mass or less, more preferably 500 ppm by mass or less. Within these ranges, it is advantageous since it becomes relatively easy to prepare a composition that satisfies the requirements of the present invention.
[0162] [Manufacturing method for resin lenses for head mounted displays] The resin lens for head mounted displays of the present embodiment is formed by molding the above resin composition. As a method for producing the resin lens for head mounted displays of the present embodiment, a molding method such as injection molding, compression molding, extrusion molding, etc. can be used. Among these, injection molding is preferred from the viewpoint of productivity.
[0163] Typically, injection molding consists of (1) an injection process in which resin is melted and the molten resin is filled into the cavity of a temperature-controlled mold; (2) a pressure holding process in which pressure is applied inside the cavity until the gate is sealed, and an amount of resin is injected equivalent to the amount of molten resin filled in the injection process that comes into contact with the mold and cools and shrinks; (3) a cooling process in which the molded product is held until the resin has cooled after the pressure holding process is released; and (4) the mold is opened and the cooled molded product is removed.
[0164] In this case, the molding temperature is preferably in the range of Tg+100°C to Tg+160°C, preferably in the range of Tg+110°C to Tg+150°C, based on the glass transition temperature (Tg) of the resin composition. Here, the molding temperature refers to the controlled temperature of a band heater wrapped around the injection nozzle. The higher the molding temperature, the lower the retardation of the resin lens that can be obtained. However, at a constant temperature, coloring due to thermal degradation during retention in the molding machine is promoted, so that the molding temperature should be appropriately selected. The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-20°C, based on the glass transition temperature (Tg) of the resin composition.
[0165] The injection speed can be appropriately selected depending on the thickness and dimensions of the resin lens to be obtained, and can be appropriately selected, for example, from the range of 5 to 1000 mm / sec. The pressure for maintaining the pressure can be appropriately selected depending on the shape of the resin lens to be obtained, and can be appropriately selected within the range of, for example, 30 to 120 MPa. The pressure for holding the pressure referred to here is the pressure maintained by a screw for further feeding the molten resin from the gate after the molten resin has been filled.
[0166] In addition, an annealing step may be performed to relax residual stress caused by injection molding and reduce the phase difference of the resin lens. The annealing temperature is preferably in the range of Tg-50°C to Tg, and more preferably in the range of Tg-30°C to Tg-10°C, based on the glass transition temperature (Tg) of the resin composition.
[0167] The surface of the resin lens for head mounted displays of the present embodiment may be further subjected to a surface functionalization treatment such as a hard coat treatment, an antireflection treatment, a transparent conductive treatment, an electromagnetic wave shielding treatment, a gas barrier treatment, etc. The thickness of these functional layers is not particularly limited, but is usually in the range of 0.01 to 10 μm.
[0168] The hard coat layer to be applied to the surface can be formed, for example, by applying a coating liquid prepared by dissolving or dispersing an acrylate such as a silicone-based curable resin, an organic polymer composite inorganic fine particle-containing curable resin, a urethane acrylate, an epoxy acrylate, or a polyfunctional acrylate, and a photopolymerization initiator in an organic solvent, onto a film or sheet obtained from the resin composition of the present embodiment by a conventionally known coating method, drying the coating, and photocuring the coating. In addition, before applying the hard coat layer, in order to improve adhesion, for example, a method of forming an easy-adhesion layer, a primer layer, an anchor layer, or the like containing inorganic fine particles in its composition and then forming the hard coat layer can be used. The antiglare layer applied to the surface is formed by forming fine particles of silica, melamine resin, acrylic resin or the like into an ink, applying it onto the other functional layers by a conventionally known application method, and curing it with heat or light. Examples of the anti-reflection layer applied to the surface include thin films of inorganic materials such as metal oxides, fluorides, silicides, borides, nitrides, and sulfides, and single or multiple layers of resins with different refractive indexes such as acrylic resins and fluororesins. Also usable are thin layers containing composite fine particles of inorganic compounds and organic compounds. EXAMPLES
[0169] The following are examples. , reference example The present invention will be described in detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.
[0170] <1. Measurement of the amount of 2-cyclohexylamino-N-cyclohexylsuccinimide in N-cyclohexylmaleimide> N-cyclohexylmaleimide or N-cyclohexylmaleimide / meta-xylene solution was collected and weighed to prepare a 25% by mass N-cyclohexylmaleimide meta-xylene solution, to which isopropyl benzoate was added as an internal standard substance. Measurement was performed using gas chromatography (Shimadzu GC-2014) under the following conditions to determine the content. Detector: FID Column used: HP-5ms Measurement conditions: After holding at 80°C for 5 minutes, increase the temperature to 300°C at a rate of 10°C / min, and then hold for 5 minutes.
[0171] <2. Measurement of the amount of 2-anilino-N-phenylsuccinimide in N-phenylmaleimide> N-phenylmaleimide or N-phenylmaleimide / meta-xylene solution was collected and weighed to prepare a 10% by mass N-phenylmaleimide solution in meta-xylene. Isopropyl benzoate was added as an internal standard substance, and the content was measured and determined using liquid chromatography (Waters UPLC H-class) under the following conditions. Detector: PDA (detection wavelength: 210nm to 300nm) Column used: ACQUITY UPLC HSS T3 Column temperature: 40℃ Mobile phase: 50% acetonitrile aqueous solution containing 0.1% formic acid Flow rate: 0.4mL / min
[0172] <3. Determination of remaining amount of N-substituted maleimide monomer> A portion of the object to be analyzed (polymerization solution after polymerization or methacrylic resin pellets) was collected and weighed, and this sample was dissolved in chloroform to prepare a 5% by mass solution. n-Decane was added as an internal standard substance, and the content was measured and determined using gas chromatography (Shimadzu GC-2010) under the following conditions. Detector: FID Column used: ZB-1 Measurement conditions: After holding at 45°C for 5 minutes, heat up to 300°C at a rate of 20°C / min, then hold for 15 minutes
[0173] <4. Analysis of structural units> The manufacturing examples described below , manufacturing reference example and manufacturing Unless otherwise specified, each structural unit in the methacrylic resin produced in the comparative example is 1 H-NMR measurement and 13By C-NMR measurement, each structural unit in the methacrylic resin and the methacrylic resin composition was identified, and the amount of each structural unit was calculated. 1 H-NMR measurement and 13 The measurement conditions for C-NMR measurement are as follows: Measuring equipment: JNM-ECZ400S manufactured by JEOL Ltd. Measurement solvent: CDCl3 or d6-DMSO ·Measurement temperature: 40℃
[0174] <5. Molecular weight and molecular weight distribution> The manufacturing examples described below , manufacturing reference example The weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) of the methacrylic resin compositions produced in the comparative production examples were measured using the following apparatus and under the following conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were connected in series. Column temperature: 40℃ The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard at 0.1 g / L. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Sample: 0.02 g of methacrylic resin composition dissolved in 20 mL of tetrahydrofuran Injection volume: 10μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin composition. Based on each calibration curve obtained by measuring the standard samples for the calibration curve, the weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) of the methacrylic resin composition were determined, and the molecular weight distributions (Mw / Mn) and (Mz / Mw) were determined using these values.
[0175] <6. Phase difference within the effective diameter of the resin lens> Working Example , reference example For the resin lenses obtained in the above and comparative examples, the surface distribution of the phase difference of the lenses was measured from the optical axis direction at a wavelength of 520 nm using a birefringence evaluation system PA-200-L manufactured by Photonic Lattice, and the average absolute value (nm) of the phase difference was calculated by specifying an area within the effective diameter (Φ41 mm) of the lens.
[0176] <7. Content of fluorescent substances in resin lenses> Working Example , reference example The resin lenses obtained in the comparative examples were shredded, weighed into a glass sample bottle, chloroform was added, and the bottle was shaken at a speed of 800 revolutions per minute for 30 minutes to prepare a 2.0 mass % chloroform solution of the resin lenses. The fluorescence intensity was measured using a fluorescence spectrophotometer (Fluorolog3-22, manufactured by Horiba Jobin Yvon). The measurement conditions were as follows: a xenon lamp as the light source, a PMT as the detector, an excitation wavelength of 436 nm, a slit width of 2 nm on both the excitation and observation sides, a time constant of 0.2 s, and a measurement mode of Sc / Rc, which normalizes the emission intensity by the excitation light intensity of each wavelength. Measurements were performed with a quartz cell with an optical path length of 1 cm and observation at 90°. The obtained fluorescence intensity at a wavelength of 530 nm was normalized using the fluorescence intensity of a fluorescein / ethanol solution as follows. Ethanol and 5×10 -8 mol / L and 1×10 -6 The fluorescence intensity at 530 nm was obtained when each mol / L fluorescein / ethanol solution was spectroscopically analyzed at an excitation wavelength of 436 nm, and after subtracting the background of ethanol, a concentration-intensity conversion formula was created. The fluorescence emission spectrum of chloroform was measured, and the emission intensity obtained by subtracting the emission intensity at 530 nm of chloroform from the emission intensity at 530 nm of the 2.0 mass% chloroform solution of the resin lens was converted into a concentration using the concentration-intensity conversion formula for the fluorescein / ethanol solution obtained above, and the content of the fluorescent substance (mol / L) was calculated.
[0177] <8. Glass transition temperature of resin lenses> The glass transition temperature (Tg) (°C) of the resin lens was measured in accordance with JIS-K7121. First, from a resin lens that had been conditioned (left at 23° C. for one week) under standard conditions (23° C., 50% RH), test pieces of about 10 mg each were cut out at four points (four locations). Next, a differential scanning calorimeter (PerkinElmer Japan Diamond DSC) was used under the condition of a nitrogen gas flow rate of 25 mL / min, where the sample was heated from room temperature (23°C) to 200°C (first heating) at 10°C / min, held at 200°C for 5 minutes to completely melt the sample, then cooled from 200°C to 40°C at 10°C / min, held at 40°C for 5 minutes, and heated again under the above heating conditions (second heating). The intersection (midpoint glass transition temperature) between the step-like change partial curve during the second heating and a straight line equidistant in the vertical direction from each baseline extension line was measured as the glass transition temperature (Tg) (°C). Four measurements were taken per sample, and the arithmetic average (rounded off to the nearest whole number) of the four measurements was taken as the measured value.
[0178] <9. Photoelastic coefficient of resin lens> Working Example , reference exampleThe resin lenses obtained in the comparative examples were each cut into small pieces, and then pressed into films using a vacuum compression molding machine to prepare measurement samples. Specific sample preparation conditions were as follows: using a vacuum compression molding machine (Shinto Metal Industries, SFV-30 model), preheating at 260°C and reduced pressure (approximately 10 kPa) for 10 minutes, compressing the resin lens at 260°C and approximately 10 MPa for 5 minutes, releasing the reduced pressure and pressing pressure, and transferring it to a cooling compression molding machine for cooling and solidification. The obtained pressed film was aged for 24 hours or more in a constant temperature and humidity room adjusted to 23°C and humidity 60%, and then a test specimen (approximately 150 μm thick and 6 mm wide) for measurement was cut out. The photoelastic coefficient C was measured using a birefringence measuring device described in detail in Polymer Engineering and Science 1999, 39, 2349-2357. R (Pa -1 ) was measured. The film-like test piece was placed on a film tensioning device (manufactured by Imoto Manufacturing Co., Ltd.) similarly installed in a constant temperature and humidity chamber so that the distance between the chucks was 50 mm. Next, a birefringence measuring device (manufactured by Otsuka Electronics, RETS-100) was placed so that the laser light path of the device was located at the center of the film, and the birefringence of the test piece was measured while applying a tensile stress at a strain rate of 50% / min (distance between chucks: 50 mm, chuck movement speed: 5 mm / min). The birefringence (Δn) and tensile stress (σ R ) from the relationship between the photoelastic coefficient (C R )(Pa -1 ) was calculated. For the calculation, the tensile stress was set to 2.5MPa or less. R Data between ≦10 MPa were used. C R =Δn / σ R Here, the birefringence (Δn) has the value shown below. Δn=nx-ny (nx: refractive index in the stretching direction, ny: refractive index in the in-plane direction perpendicular to the stretching direction)
[0179] <10. Light transmittance of resin lenses> Working Example , reference exampleThe resin lenses obtained in the above and comparative examples were measured for transmittance (%) at 5 nm intervals in the wavelength range of 380 to 780 nm with a D65 light source and a 10° field of view, with the light source passing through the thickest part of the lens in the thickness direction, using a spectrophotometer (SD-5000, manufactured by Nippon Denshoku Industries Co., Ltd.). Using the measured values, the ratio (T450 / T680) of the transmittance (T450) at a wavelength of 450 nm to the transmittance (T680) at a wavelength of 680 nm was calculated.
[0180] <11.Image clarity> Working Example , reference example Using the resin lenses obtained in the above and comparative examples, a simulation device reproducing the principle of the head mounted display described in JP 2017-21321 A, as shown in FIG. 1, was produced in a dark room. The simulation device includes a liquid crystal display 1, a polarizing plate 2, a quarter-wave plate 3, a half mirror 4, and an embodiment , reference example The resin lens 5, the quarter-wave plate 6, and the reflective polarizing plate 7 obtained by the comparative example are arranged on the same axis in this order. The light along the optical axis from the liquid crystal display 1 passes through the polarizing plate 2, the quarter-wave plate 3, the half mirror 4, the resin lens 5, and the quarter-wave plate 6 to reach the reflective polarizing plate 7, where it is reflected by the reflective polarizing plate 7 (first reflection), and then passes through the quarter-wave plate 6 and the resin lens 5 to reach the half mirror 4, where it is reflected by the half mirror 4 (second reflection), and again passes through the resin lens 5, the quarter-wave plate 6, and the reflective polarizing plate 7 to reach the human eye. The half mirror 4 allows a portion of the light to be reflected and the remaining light to be transmitted. The light increases the phase delay of 90 degrees each time it passes through the quarter-wave plate. The image is enlarged by the above two reflections and reaches the human eye. A still image displayed on the liquid crystal display 1 was observed through the simulator, and the clarity of the image was evaluated according to the following evaluation criteria. [Evaluation Criteria] A: The image is enlarged and there is no bleeding or blurring. △: The enlarged image is overlapped with a lower magnification image, making the image somewhat unclear. ×: Images with low magnification are mainly seen and are unclear.
[0181] [Raw materials] The following examples , reference example The raw materials used in the comparative examples are shown below. [[monomer]] Methyl methacrylate (MMA): Asahi Kasei Corporation N-Cyclohexylmaleimide (chMI): Nippon Shokubai Co., Ltd. (The mass ratio of 2-cyclohexylamino-N-cyclohexylsuccinimide (CCSI) to the mass of ChMI is 80 ppm by mass.) N-Phenylmaleimide (phMI): Nippon Shokubai Co., Ltd. (The mass ratio of 2-anilino-N-phenylsuccinimide (APSI) to pHMI mass is 60 ppm by mass)
[0182] -Pretreatment of N-substituted maleimide (chMI, phMI) (washing process and dehydration process)- The above N-cyclohexylmaleimide (chMI) and N-phenylmaleimide (phMI) were subjected to the following water washing and dehydration steps to remove 2-amino-N-substituted succinimides (CCSI, APSI) and water contained therein.
[0183] --Washing and dehydration of N-cyclohexylmaleimide (chMI)-- ---Reducing CCSI in N-cyclohexylmaleimide to 5 ppm by mass or less--- 250.0 kg of chMI and 750.0 kg of meta-xylene (hereinafter referred to as "mXy") were weighed and placed in a 2.0m 3 The mixture was added to a glass-lined reactor, and steam was blown into the jacket to raise the solution temperature in the reactor to 56°C, followed by stirring to obtain an organic layer. Next, 350.0 kg of 2% by mass sulfuric acid water was weighed and added to the reactor, and the solution temperature was kept at 56°C and stirred at 100 rpm for 10 minutes. The stirring was stopped, the mixture was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum. The same procedure was repeated two more times, and the organic layer was washed with aqueous sulfuric acid three times in total. The amount of CCSI in the organic layer was quantified by gas chromatography, and found to be 4.9 ppm by mass relative to chMI in the organic layer. Thereafter, 350.0 kg of ion-exchanged water was added to the reactor, and the solution was stirred at 100 rpm for 10 minutes while maintaining the solution temperature at 55° C. The stirring was stopped, the solution was allowed to stand for 20 minutes, and the aqueous layer was extracted into a drum can. The same procedure was repeated once more, and the organic layer was washed with ion-exchanged water twice in total. The amount of CCSI in the organic layer was quantified by gas chromatography, and found to be 4.6 ppm by mass relative to chMI in the organic layer. Next, the solution temperature was kept at 50° C., and the pressure in the reactor was gradually reduced while stirring at 100 rpm, to 5 kPa. The solution temperature was then raised to 60° C., and azeotropic dehydration was performed. 131.6 kg of the water / mXy mixture was distilled off, and the water concentration in the organic layer was quantified with a Karl Fischer moisture meter, which was 102 ppm by mass relative to the mass of the organic layer. Concentration adjusting agent mXy was added to the organic layer to obtain 1,034.3 kg of an organic layer having a chMI of 24.0 mass %, a water concentration of 191 mass ppm, and a CCSI of 4.6 mass ppm relative to the mass of chMI.
[0184] ---Reducing CCSI in N-cyclohexylmaleimide to 1 ppm by mass or less--- 80.0 kg of chMI and 240.0 kg of mXy were weighed and placed in a 0.50 m 3 The mixture was added to a glass-lined reactor, and steam was blown into the jacket to raise the solution temperature in the reactor to 55°C, followed by stirring to obtain an organic layer. Next, 112.0 kg of 2% by mass sulfuric acid water was weighed and added to the reactor, and the solution temperature was kept at 55°C and stirred at 100 rpm for 30 minutes. The stirring was stopped, the mixture was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum. The same procedure was repeated three more times, and the organic layer was washed with aqueous sulfuric acid four times in total. The amount of CCSI in the organic layer was quantified by gas chromatography, and found to be 0.57 ppm by mass relative to chMI in the organic layer. Thereafter, 112.0 kg of ion-exchanged water was added to the reactor, and the solution was stirred at 100 rpm for 30 minutes while maintaining the solution temperature at 55° C. The stirring was stopped, the solution was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum can. The solution temperature was kept at 50° C., and the pressure in the reactor was gradually reduced while stirring at 100 rpm, until the pressure in the reactor reached 5 kPa. The solution temperature was then raised to 60° C., and azeotropic dehydration was performed. 54 kg of the water / mXy mixture was distilled off, and the water concentration in the organic layer was quantified using a Karl Fischer moisture meter, which was 46 ppm by mass relative to the mass of the organic layer. Concentration adjusting agent mXy was added to the organic layer to obtain 384.0 kg of an organic layer having a chMI of 20.3 mass %, a water concentration of 125 mass ppm, and a CCSI of 0.60 mass ppm relative to the mass of chMI.
[0185] --Washing and dehydration of N-phenylmaleimide (phMI)-- ---Reducing APSI in N-phenylmaleimide to 5 ppm by mass or less--- 150.0 kg of phMI and 720.0 kg of mXy were weighed out and placed in a 2.0m 3 The mixture was added to a glass-lined reactor, and steam was blown into the jacket to raise the solution temperature in the reactor to 55°C, followed by stirring to obtain an organic layer. Next, 336.0 kg of 7% by mass sodium bicarbonate water was weighed and added to the reactor, and the solution temperature was kept at 55°C and stirred at 100 rpm for 10 minutes. The stirring was stopped, the mixture was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum. Next, 336.0 kg of ion-exchanged water was added to the reactor, and the solution was stirred at 100 rpm for 10 minutes while maintaining the solution temperature at 55° C. The stirring was stopped, the solution was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum can. Thereafter, 336.0 kg of 2% by mass aqueous sulfuric acid was weighed and added to the reactor, and the solution was stirred at 100 rpm for 10 minutes while maintaining the solution temperature at 55° C. The stirring was stopped, the solution was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum can. The same washing operation with ion-exchanged water was carried out two more times in the same manner as above. The amount of APSI in the organic layer was quantified by liquid chromatography and found to be 3.6 ppm by mass relative to the pHMI in the organic layer. Next, the solution temperature was kept at 50° C., and the pressure in the reactor was gradually reduced while stirring at 100 rpm, until the pressure in the reactor reached 5 kPa. The solution temperature was then raised to 55° C., and azeotropic dehydration was performed. 190 kg of the water / mXy mixture was distilled off, and the water concentration in the organic layer was quantified using a Karl Fischer moisture meter, which was 47 ppm by mass relative to the mass of the organic layer. Concentration adjusting agent mXy was added to the organic layer to obtain 1,340.7 kg of an organic layer having a pHMI of 10.8 mass %, a water concentration of 170 mass ppm, and an APSI of 3.4 mass ppm relative to the mass of pHMI.
[0186] ---Reducing APSI in N-phenylmaleimide to 1 ppm by mass or less--- 50.0 kg of phMI and 240.0 kg of mXy were weighed and placed in a 0.50 m 3 The mixture was added to a glass-lined reactor, and steam was blown into the jacket to raise the solution temperature in the reactor to 55°C, followed by stirring to obtain an organic layer. Next, 112.0 kg of 7% by mass sodium bicarbonate water was weighed and added to the reactor, and the solution temperature was kept at 55°C and stirred at 100 rpm for 15 minutes. The stirring was stopped, the mixture was left to stand for 10 minutes, and the aqueous layer was extracted into a drum. The same operation was repeated once more, and the organic layer was washed with sodium bicarbonate water twice in total. Next, 112.0 kg of ion-exchanged water was added to the reactor, and the solution was stirred at 100 rpm for 30 minutes while maintaining the solution temperature at 55° C. The stirring was stopped, the solution was allowed to stand for 10 minutes, and the aqueous layer was extracted into a drum can. Then, 112.0 kg of 2% by mass sulfuric acid water was weighed and added to the reactor, and the solution temperature was kept at 55° C. and stirred at 100 rpm for 30 minutes. The stirring was stopped, the mixture was left to stand for 10 minutes, and the aqueous layer was extracted into a drum. The same operation was repeated two more times, and the organic layer was washed with sulfuric acid water three times in total. The same washing operation with ion-exchanged water was carried out two more times in the same manner as above. The amount of APSI in the organic layer was quantified by liquid chromatography and found to be 0.37 ppm by mass relative to the pHMI in the organic layer. The solution temperature was kept at 50° C., and the pressure in the reactor was gradually reduced while stirring at 100 rpm, until the pressure in the reactor reached 5 kPa. The solution temperature was then raised to 55° C., and azeotropic dehydration was performed. 72 kg of the water / mXy mixture was distilled off, and the water concentration in the organic layer was quantified using a Karl Fischer moisture meter, which was 60 ppm by mass relative to the mass of the organic layer. Concentration adjusting agent mXy was added to the organic layer to obtain 432.8 kg of an organic layer having a pHMI of 10.3 mass %, a water concentration of 180 mass ppm, and an APSI of 0.42 mass ppm relative to the mass of pHMI.
[0187] [[Polymerization initiator]] 1,1-Di(t-butylperoxy)cyclohexane: NOF Corporation's "Perhexa C" [[Chain transfer agent]] n-Octyl mercaptan: Kao Corporation [[Hindered phenolic antioxidant]] Irganox 1010: BASF [[Phosphorus-based antioxidant]] Irgafos 168 (melting point 180-190°C): manufactured by BASF
[0188] [Methacrylic resin composition] [Manufacturing reference Example 1] 374.8 kg of a 10.3 mass% mXy solution of phMI (APSI was 0.42 mass ppm relative to the mass of phMI) that had been subjected to the water washing process and dehydration process, and 323.6 kg of a 20.3 mass% mXy solution of chMI (CCSI was 0.60 mass ppm relative to the mass of chMI) that had been subjected to the water washing process and dehydration process were weighed, and these were then poured into a 1.25 m 3 The mixture was added to the reactor, and 160.8 kg of mXy was distilled off under reduced pressure while stirring at a solution temperature of 60°C and a pressure inside the reactor of 5 kPa. The reactor was then returned to normal pressure, and 16.7 kg of mXy was added to prepare a mixed solution of 38.6 kg of phMI, 65.7 kg of chMI, and 450.0 kg of mXy. 445.7 kg of MMA and 0.413 kg of n-octyl mercaptan, a chain transfer agent, were weighed, charged, and stirred to obtain a monomer mixed solution. The liquid in the reactor was subjected to nitrogen bubbling at a rate of 30 L / min for 1 hour to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 125°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.23 kg of 1,1-di(t-butylperoxy)cyclohexane in 2.77 kg of mXy at a rate of 0.5 kg / hour while stirring at 50 rpm, and the addition was stopped 6 hours after the start of polymerization. During the polymerization, the solution temperature in the reactor was controlled at 125±2° C. by temperature regulation using a jacket. After 8 hours had passed since the start of polymerization, a polymerization solution containing a methacrylic resin having a ring structure in the main chain was obtained. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained phMI at 1,340 ppm by mass and chMI at 4,390 ppm by mass. To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added with stirring, based on 100 mass % of the polymer contained in the solution. This polymerization solution containing the antioxidant was filtered through a filter made of SUS316L metal fiber with a filtration accuracy of 2 μm. The equipment used in the volatilization process to recover the polymer from the polymerization solution is a flat plate heat exchanger with a flat plate slit-type flow path and a heat transfer medium flow path, and an internal volume of approximately 0.3 m. 3 The devolatilization apparatus used was composed of a SUS heat medium jacketed reduced pressure vessel (hereinafter referred to as the devolatilization tank). The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed on the top of the vacuum vessel at a rate of 30 L / h and heated to 260°C. It was then supplied to a volatilization vessel that was heated and evacuated to an internal temperature of 260°C and a vacuum of 30 Torr, and subjected to volatilization treatment. The shear rate in the volatilization vessel was calculated to be 5.3 s from the shape of the vessel and the operating conditions. -1 It was. The polymer after devolatilization was pressurized from the bottom of the devolatilization tank with a gear pump, extruded through a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition A. The composition of the methacrylic resin composition A was confirmed to be 81.2 mass%, 7.1 mass%, and 11.7 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 148,000, Mw / Mn was 2.12, Mz / Mw was 1.63, and the glass transition temperature was 133°C.
[0189] [Production Example 2] 352.4 kg of a 10.3 mass% mXy solution of phMI (APSI was 0.42 mass ppm relative to the mass of phMI) that had been through the water washing process and dehydration process, and 310.3 kg of a 20.3 mass% mXy solution of chMI (CCSI was 0.60 mass ppm relative to the mass of chMI) that had been through the water washing process and dehydration process were weighed out, and these were then poured into a 1.25 m 3 The mixture was added to the reactor, and 335.4 kg of mXy was distilled off under reduced pressure while stirring at a solution temperature of 60°C and a pressure inside the reactor of 5 kPa. The reactor was then returned to normal pressure, and 8.9 kg of mXy was added to prepare a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octyl mercaptan, a chain transfer agent, were weighed, charged, and stirred to obtain a monomer mixed solution. Then 123.1 kg of mXy was weighed out and added to Tank 1. Furthermore, 110.0 kg of MMA and 90.0 kg of mXy were weighed and stirred in tank 2 to prepare a monomer solution for additional addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and tank 1 and tank 2 were each bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 128°C, and polymerization was started by adding a polymerization initiator solution prepared by dissolving 0.37 kg of 1,1-di(t-butylperoxy)cyclohexane in 3.005 kg of mXy at a rate of 1 kg / hour while stirring at 50 rpm. 0.5 hours after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour, and mXy was added from Tank 1 at 35.2 kg / hour for 3.5 hours. During the polymerization, the solution temperature in the reactor was controlled at 128±2° C. by temperature regulation using a jacket. Then, 4 hours after the initiation of polymerization, the addition rate of the initiator solution was changed to 0.75 kg / hour, and the monomer solution containing MMA was added from Tank 2 at a rate of 100.0 kg / hour for 2 hours. Further, 6 hours after the start of polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour, and 7 hours after the start of polymerization, the addition was stopped. The polymerization was continued for another hour to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in the main chain. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained 220 ppm by mass of phMI and 1,070 ppm by mass of chMI. To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added with stirring, based on 100 mass % of the polymer contained in the solution. The polymerization solution containing the antioxidant was filtered through a filter made of SUS316L metal fiber with a filtration accuracy of 2 μm. The equipment used in the volatilization process to recover the polymer from the polymerization solution is a flat plate heat exchanger with a flat plate slit-type flow path and a heat transfer medium flow path, and an internal volume of approximately 0.3 m. 3The devolatilization apparatus used was composed of a SUS heat medium jacketed reduced pressure vessel (hereinafter referred to as the devolatilization tank) and had no rotating part. The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed at the top of the vacuum vessel at a rate of 30 L / h, heated to 260°C, and then supplied to a volatilization vessel that had been heated and evacuated to an internal temperature of 260°C and a vacuum of 30 Torr, where it was subjected to volatilization treatment. The shear rate in the volatilization vessel was calculated to be 5.3 s from the shape of the vessel and the operating conditions. -1 It was. The polymer after devolatilization was pressurized from the bottom of the devolatilization tank with a gear pump, extruded through a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition B. The composition of the methacrylic resin composition B was confirmed to be 80.9 mass%, 7.0 mass%, and 12.1 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 142,000, Mw / Mn was 2.32, Mz / Mw was 1.75, and the glass transition temperature was 134°C.
[0190] [Production Example 3] A 10.8 mass% mXy solution (APSI was 3.4 mass ppm relative to the mass of phMI) was used as phMI that had been subjected to a water-washing process and a dehydration process, and a 24.0 mass% mXy solution (CCSI was 4.6 mass ppm relative to the mass of chMI) was used as chMI that had been subjected to a water-washing process and a dehydration process. Except for the composition of the mixed solution prepared in the reactor being the same as in Production Example 2, a methacrylic resin composition C was obtained in the same manner as in Production Example 2. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained 210 ppm by mass of phMI and 1090 ppm by mass of chMI. The composition of the methacrylic resin composition C was confirmed to be 80.8 mass%, 7.1 mass%, and 12.1 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 141,000, Mw / Mn was 2.31, Mz / Mw was 1.75, and the glass transition temperature was 134°C.
[0191] [Production Example 4] In a reactor equipped with a jacket-based temperature control device and an agitator, 40 parts by mass of MMA, 60 parts by mass of mXy, and 0.08 parts by mass of n-octyl mercaptan, a chain transfer agent, were charged, and nitrogen bubbling was performed for 1 hour to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 120 ° C., and while stirring at 50 rpm, a polymerization initiator solution in which 0.02 parts by mass of 1,1-di(t-butylperoxy)cyclohexane was dissolved in 0.10 parts by mass of mXy was added at a constant speed for 5 hours to polymerize, and the mixture was further aged at 120 ° C. for 3 hours, and the polymerization was terminated 8 hours after the start of polymerization to obtain a PMMA mXy solution. After the polymerization was completed, the liquid temperature was lowered to 50 ° C. Next, a mixed liquid consisting of 12 parts by mass of monomethylamine and 12 parts by mass of methanol was dropped into the reactor at room temperature, and the liquid temperature was raised to 170° C. and stirred under pressure for 1 hour to allow the glutarimide cyclization reaction to proceed. The liquid temperature was lowered to 120° C., and the inside of the reactor was reduced in pressure to distill off unreacted monomethylamine and methanol, as well as a portion of mXy, to obtain a glutarimide-cyclized methacrylic polymer solution containing about 50% by mass of mXy. To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added with stirring, based on 100 mass % of the polymer contained in the solution. The polymerization solution containing the antioxidant was filtered through a filter made of SUS316L metal fiber with a filtration accuracy of 2 μm. The equipment used in the volatilization process to recover the polymer from the polymerization solution is a flat plate heat exchanger with a flat plate slit-type flow path and a heat transfer medium flow path, and an internal volume of approximately 0.3 m. 3 The devolatilization apparatus used was composed of a SUS heat medium jacketed reduced pressure vessel (hereinafter referred to as the devolatilization tank) and had no rotating part. The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed at the top of the vacuum vessel at a rate of 30 L / h, heated to 260°C, and then supplied to a volatilization vessel that had been heated and evacuated to an internal temperature of 260°C and a vacuum of 30 Torr, where it was subjected to volatilization treatment. The shear rate in the volatilization vessel was calculated to be 5.3 s from the shape of the vessel and the operating conditions. -1 It was. The polymer after the devolatilization was pressurized from the bottom of the devolatilization tank with a gear pump, extruded through a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition D. The composition of the obtained methacrylic resin composition D was confirmed to be 3.2% imidization rate, 5.1% by mass glutarimide structural unit content, 93,000 weight average molecular weight Mw, 1.79 Mw / Mn, 1.51 Mz / Mw, and 122°C glass transition temperature.
[0192] [Production Example 5] A methacrylic resin composition E was obtained in the same manner as in Production Example 2, except that the amounts of each monomer in the solution prepared in the reactor were phMI 39.3 kg, chMI 46.5 kg, and MMA 354.2 kg. The composition of the methacrylic resin composition E was confirmed to be 83.2 mass%, 7.6 mass%, and 9.2 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 143,000, Mw / Mn was 2.35, Mz / Mw was 1.81, and the glass transition temperature was 132°C.
[0193] [Comparative Manufacturing Example 1] 352.4 kg of a 10.3 mass% mXy solution of phMI (APSI was 0.42 mass ppm relative to the mass of phMI) that had been through the water washing process and dehydration process, and 310.3 kg of a 20.3 mass% mXy solution of chMI (CCSI was 0.60 mass ppm relative to the mass of chMI) that had been through the water washing process and dehydration process were weighed out, and these were then poured into a 1.25 m 3 The mixture was added to the reactor, and 335.4 kg of mXy was distilled off under reduced pressure while stirring at a solution temperature of 60°C and a pressure inside the reactor of 5 kPa. The reactor was then returned to normal pressure, and 8.9 kg of mXy was added to prepare a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octyl mercaptan, a chain transfer agent, were weighed, charged, and stirred to obtain a monomer mixed solution. Then 123.1 kg of mXy was weighed out and added to Tank 1. Furthermore, 110.0 kg of MMA and 90.0 kg of mXy were weighed and stirred in tank 2 to prepare a monomer solution for additional addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and tank 1 and tank 2 were each bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 128°C, and polymerization was started by adding a polymerization initiator solution prepared by dissolving 0.37 kg of 1,1-di(t-butylperoxy)cyclohexane in 3.005 kg of mXy at a rate of 1 kg / hour while stirring at 50 rpm. 0.5 hours after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour, and mXy was added from Tank 1 at 35.2 kg / hour for 3.5 hours. During the polymerization, the solution temperature in the reactor was controlled at 128±2° C. by temperature regulation using a jacket. Then, 4 hours after the initiation of polymerization, the addition rate of the initiator solution was changed to 0.75 kg / hour, and the monomer solution containing MMA was added from Tank 2 at a rate of 100.0 kg / hour for 2 hours. Further, 6 hours after the start of polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour, and 7 hours after the start of polymerization, the addition was stopped. The polymerization was continued for another hour to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in the main chain. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained 220 ppm by mass of phMI and 1,070 ppm by mass of chMI. To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added with stirring, based on 100 mass % of the polymer contained in the solution. The polymerization solution containing the antioxidant was filtered through a filter made of SUS316L metal fiber with a filtration accuracy of 2 μm. Next, the obtained polymerization solution was introduced into a twin-screw extruder equipped with multiple vents for devolatilization, whereby devolatilization was carried out. The obtained polymerization solution was fed into the twin-screw extruder so as to be 10 kg / hour in terms of resin, and the conditions were a barrel temperature of 260°C, a screw rotation speed of 150 rpm, and a vacuum degree of 10 to 40 Torr. The resin devolatilized by the twin-screw extruder was extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition F. The shear rate in the devolatilizer was calculated from the shape of the device and the operating conditions to be 80 s -1 It was. The composition of the methacrylic resin composition F was confirmed to be 80.9 mass%, 7.0 mass%, and 12.1 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 136,000, Mw / Mn was 2.35, Mz / Mw was 1.81, and the glass transition temperature was 134°C.
[0194] [Comparative Manufacturing Example 2] A methacrylic resin composition G was obtained in the same manner as in Production Example 2, except that a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy was prepared by using commercially available unpurified products as phMI and chMI. The shear rate in the volatilizer was calculated to be 5.3 s from the shape of the apparatus and the operating conditions. -1 It was. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained 220 ppm by mass of phMI and 1070 ppm by mass of chMI. The composition of the obtained pellet-like polymer was confirmed to be 80.9 mass%, 7.1 mass%, and 12.1 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight Mw was 142,000, Mw / Mn was 2.32, Mz / Mw was 1.75, and the glass transition temperature was 134°C.
[0195] [Comparative Manufacturing Example 3] Commercially available unpurified phMI and chMI were used. 38.6 kg of phMI, 65.7 kg of chMI, 450.0 kg of mXy, 445.7 kg of MMA, and 0.413 kg of n-octyl mercaptan as a chain transfer agent were weighed out and mixed in a 1.25 m 3 The mixture was charged into a reactor and stirred to obtain a monomer mixture solution. The liquid in the reactor was subjected to nitrogen bubbling at a rate of 30 L / min for 1 hour to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 125°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.23 kg of 1,1-di(t-butylperoxy)cyclohexane in 2.77 kg of mXy at a rate of 0.5 kg / hour while stirring at 50 rpm, and the addition was stopped 6 hours after the start of polymerization. During the polymerization, the solution temperature in the reactor was controlled at 125±2° C. by temperature regulation using a jacket. After 8 hours had passed since the start of polymerization, a polymerization solution containing a methacrylic resin having a ring structure in the main chain was obtained. The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and it was found that the solution contained phMI at 1,340 ppm by mass and chMI at 4,390 ppm by mass. To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added with stirring, based on 100 mass % of the polymer contained in the solution. This polymerization solution containing the antioxidant was filtered through a filter made of SUS316L metal fiber with a filtration accuracy of 2 μm. The polymerization solution to which the antioxidant was added was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer that had been preheated to 170°C, and the concentration of the polymer contained in the solution was increased to 70% by mass. The resulting polymerization solution was then concentrated in a tubular heat exchanger having a heat transfer area of 0.2 m 2 The mixture was fed to a thin-film evaporator having a rotating part and subjected to devolatilization. The temperature inside the device was 280°C, the feed rate was 30 L / hr, the rotation speed was 400 rpm, and the vacuum was 30 Torr. The polymer after devolatilization was pressurized by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition H. The shear rate in the thin-film evaporator having a rotating part was calculated from the device shape and operating conditions to be 3200 s -1 It was. The composition of the obtained pellet-like polymer was confirmed to be 81.0 mass%, 7.2 mass%, and 11.8 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight Mw was 136,000, Mw / Mn was 2.21, Mz / Mw was 1.71, and the glass transition temperature was 134°C.
[0196] [Comparative Manufacturing Example 4] A methacrylic resin composition I was obtained in the same manner as in Production Example 2, except that the amounts of each monomer in the solution prepared in the reactor were phMI 41.3 kg, chMI 41.3 kg, and MMA 357.5 kg. The composition of the methacrylic resin composition I was confirmed to be 84.1 mass%, 8.0 mass%, and 7.9 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight Mw was 145,000, Mw / Mn was 2.31, Mz / Mw was 1.77, and the glass transition temperature was 130°C.
[0197] [Comparative Manufacturing Example 5] Polymethyl methacrylate was imidized with monomethylamine using a co-rotating twin-screw extruder to obtain a methacrylic resin composition J having glutarimide structural units. Specifically, a 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 270°C, the screw rotation speed was set to 150 rpm, polymethyl methacrylate with a weight average molecular weight Mw of 108,000 was fed from the hopper at 20 kg / h, and nitrogen was flowed into the extruder at a flow rate of 200 mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by mass of monomethylamine was injected from the nozzle per 100 parts by mass of raw resin to carry out the imidization reaction. A reverse flight was placed at the end of the reaction zone (before the vent port) to fill the zone with resin. The by-products and excess methylamine after the reaction were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain an imide resin. Next, a 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 250°C, and the screw rotation speed was set to 150 rpm. The obtained imide resin was fed at 20 kg / hr, and the resin was melted and filled by a kneading block. Then, a mixed solution of dimethyl carbonate and triethylamine was injected from a nozzle as an esterification agent to reduce the carboxylic acid group in the resin. Dimethyl carbonate was 3.2 parts by mass and triethylamine was 0.8 parts by mass per 100 parts by mass of imide resin. A reverse flight was placed at the end of the reaction zone to fill the resin. The by-products and excess dimethyl carbonate after the reaction were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain a methacrylic resin composition J having a glutarimide structure. The imidization rate of this resin composition was 3.3%, and the content of glutarimide-based structural units was 5.2% by mass. The shear rate in the twin-screw extruder was calculated to be about 80 s from the device shape and operating conditions. -1 It was. The weight average molecular weight Mw was 96,000, Mw / Mn was 1.82, Mz / Mw was 1.48, and the glass transition temperature was 122°C.
[0198] [ Reference example 1,Working Example 2 ~5, Comparative Examples 1~5] Manufacturing Example , manufacturing reference example Using the methacrylic resin compositions A to J obtained in the comparative production examples, resin lenses were injection molded by the following method, and various characteristics were measured. The results are shown in Table 1. <Molding of resin lenses> Methacrylic resin compositions A to J were dried at 100°C for 4 hours in a forced air circulation dryer, and then injection molding was performed using a mold for a spherical plano-convex lens with a diameter of 41 mm and a radius of 98 mm (3.2 mm at the thickest part, with a side gate (0.95 mm thick, 5.0 mm wide)) with a clamping force of 50 T in an injection molding machine at a cylinder temperature of 270°C, a mold temperature of 116°C, an injection speed of 10 mm / s, and two-stage pressure dwelling, with the first stage being 50 MPa for 4 seconds and then the second stage being 30 MPa for 3 seconds, and a cooling time of 400 seconds. Further, the composition was annealed for 3 hours in an oven set at a temperature 25° C. lower than the glass transition temperature of the methacrylic resin composition.
[0199] [Table 1] [Industrial Applicability]
[0200] INDUSTRIAL APPLICABILITY The resin lens for head mounted displays of the present invention can provide clear images even in an optical system that utilizes polarized light, and can therefore contribute to making head mounted displays smaller and lighter. [Explanation of symbols]
[0201] 1: LCD display 2: Polarizing plate 3:1 / 4 wave plate 4: Half mirror 5: Plastic lens 6:1 / 4 wave plate 7:Reflective polarizing plate
Claims
1. The average absolute value of the phase difference within the effective diameter is 5 nm or less, The content of the fluorescent substance was calculated from the fluorescence intensity at a wavelength of 530 nm when the 2.0% by mass solution was dissolved in chloroform and measured at an excitation wavelength of 436 nm using the concentration-intensity conversion formula for a fluorescein ethanol solution. The content was 0.1 to 3.0 × 10 -9 mol / L, The head mounted display uses polarized light and transmits image light multiple times through repeated reflections. A resin lens for a head mounted display, comprising:
2. 2. The resin lens for a head mounted display according to claim 1, having a glass transition temperature (Tg) of more than 120° C. and not more than 160° C.
3. The absolute value of the photoelastic coefficient is 3.0 × 10 -12 P -1 The resin lens for a head mounted display according to claim 1 or 2, wherein:
4. The resin lens for a head mounted display according to any one of claims 1 to 3, comprising a methacrylic resin.
5. 5. The resin lens for a head mounted display according to claim 4, wherein the methacrylic resin comprises a methacrylic resin having a structural unit (X) having a ring structure in its main chain.
6. 6. The resin lens for head mounted displays according to claim 5, wherein the structural unit (X) comprises at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide structural unit, and a lactone ring structural unit.
7. 6. The resin lens for head mounted displays according to claim 5, wherein the structural unit (X) includes a structural unit derived from an N-substituted maleimide monomer.
8. The resin lens for a head mounted display according to claim 5 , wherein the structural unit (X) includes a glutarimide structural unit.
Citation Information
Patent Citations
Production of n-phenylmaleimide
JP1987273952A
Near-eye display optical module
JP2017021321A
Member for head-mounted displays
JP2018156081A
Methacrylic resin composition for optical member, molded body, and optical member
JP2019035015A
Wide-angle collimating optical device
US6563638B2
